GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 529253098 species occurrences available in GBIF matching the query: All data. The dataset includes 529253098 records from 12951 constituent datasets: 52359 records from Iziko. 2794 records from Collection Brachiopoda fossil SMF. 1 records from Oribates fuscus. 6541 records from Likona Invertebrates. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 517 records from Schulzentrum "Parc Hosingen". 69 records from Review of the genus Namadytes Hesse, 1969 (Insecta: Diptera: Mydidae: Syllegomydinae). 30 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1198. 269 records from BIRDRACE Kosmos-Racer. 2171 records from Harold W. Manter Laboratory of Parasitology Collection. 819 records from CABI Bioscience Nematode Collection. 7509 records from Perot Museum of Nature and Science. 197500 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 10 records from Feuchtwiesen Wippertal bei Wippra. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 1020718 records from Consortium of California Herbaria. 511 records from Coleoptera of Swierklaniec Forest. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 11 records from Waldgebiet Todtnau- Sonnhalde. 375 records from Phthiraptera. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 4 records from Fossil (SMNH-FO). 17802 records from The Bat Conservation Trust - Colony Count Survey. 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 520 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Vermes ZMK. 645788 records from Norwegian Biodiversity Information Centre - Other datasets. 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 56 records from Zitadelle Berlin-Spandau (7b). 26 records from Erhard Sopp. 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 62 records from Lebensraum Dorf. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 24 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, 63-150 µm. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 206 records from Total foraminifera counts from multinet M31/3_MSN908. 141 records from Total foraminifera counts of multinet M21/1_MSN614. 128 records from Total foraminifera counts of multinet M21/6_MSN784. 28 records from Occurrence of mammalia relicts at site Climauti II. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 1 records from Oribates picipes. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 7410 records from Helgeland Museum, Lepidoptera. 8579 records from The atlas of breeding birds in Małopolska. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" 1989-1996. 89 records from Collection Crustacea - PUM. 22 records from Dellwiger Bach (Dortmund). 48 records from Trockenrasen bei Dörndorf. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 24 records from Tauchen und Meer. 82 records from BIRDRACE Die Ziegeneier. 95 records from BIRDRACE BiBi. 54 records from Biotope im Schulumfeld. 17 records from Nachtinsekten am Muldenufer. 145 records from Assemblage of living benthic foraminifera in sediment profile GeoB4909-4. 316 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23068-3 in the Norwegian Sea. 232 records from Distribution of planktic foraminifera of sediment trap OG5. 174 records from Total foraminifera counts from multinet M31/3_MSN915. 145 records from Total foraminifera counts from multinet M32/3_MSN957. 67 records from Total foraminifera counts from M35/1_MSN1056. 215 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (forofitos). 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 77 records from Faunal assemblage of sediment core GS7603-12. 43 records from Total foraminifera counts from M35/1_MSN1045. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 102 records from Total foraminifera counts of multinet PO231/3_MSN1337. 128 records from Total foraminifera counts of multinet PO247/2_MSN1383. 180 records from Planktic foraminifera counts at CTD station PS55/080-1. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD61. 10 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 6 records from Distribution of meiobenthos in sediment core M23_149 of the northeastern Atlantic (Table 1). 9 records from Distribution of hydropolyp species on coral reefs of the Red Sea (Table 5). 641 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Northwest African upwelling area. 3 records from Nannofossil abundance of Hole 6-48A. 1 records from Murcia obsoleta. 3 records from Nannofossil abundance of Hole 94-609A. 11 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/014-4. 64 records from Palynology of a profile from Ahlequellmoor in Germany. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 156 records from Total foraminifera counts of multinet M21/1_MSN609. 165 records from Plasm bearing foraminifera counts of multinet M21/1_MSN608. 44 records from Plasm bearing foraminifera counts of multinet M21/5_MSN735. 22 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1370. 39 records from Foraminifera species abundances from tow TT007_4-MOC7. 49 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/514-18. 1698 records from Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 9 records from Phytoplankton abundance at station Sechin_2003-12-10_1, Casma, Peru. 20 records from The interstitial subsoil fauna of the medium beach level at Sarso Beach, Red Sea (Table 3). 670 records from Bulau. 2 records from Nannofossil abundance of Hole 6-49. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 134 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE293. 18077 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 9717 records from The Orchid Atlas of Western Australia. 1 records from Nothrus cynocephalus. 4904 records from Bacteria Collection in BCRC. 17934 records from Insects Collection of the Ghent University Zoology Museum. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 6 records from (Table 1) Beluga (Delphinapterus leucas) sightings in the eastern Beaufort Sea. 206 records from Herbarium BSG Hepaticopsida. 448770 records from CAS Botany (BOT). 15555 records from Biological Records Centre - Coccinellidae Data. 1433 records from (Appendix Table 1) Relative abundances of calcareous nannofossil in the total assemblage of ODP Hole 177-1090D. 146 records from Total foraminifera counts of multinet PO247/2_MSN1374. 322 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1243-1. 31 records from Planktic foraminifera of sediment core GeoB1406-4. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 3718 records from Benthos counted on dredged samples during Valdivia cruise VA53. 18 records from Smear slide analysis on sediment core GeoB4206-1. 46772 records from Tullie House Museum - Tullie House Museum Natural History Collections. . 69 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 14 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2). 29 records from Nannofossil abundance of Hole 13-132. 9 records from Nannofossil abundance of Hole 29-277. 5 records from Nannofossil abundance of Hole 74-525B. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 47 records from Nannofossil abundance of Hole 86-577. 19 records from Meiofauna abundance in sediment core 12930-036. 30008 records from Lepidoptera specimen database of Japan. 3133 records from AlgaTerra. 33 records from Familientag am Schorberg. 177 records from Antarctic Foraminiferans. 6680 records from SOMBASE PYCNOGONIDS. 20 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683B. 500 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 353 records from Size of planktic foraminifera at CTD station PS55/063. 10 records from Microzooplankton abundance and biomass at station NBP97-08-06-4. 14 records from Phytoplankton abundance during Arne Tiselius cruise AT90/1. 684 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 89 records from Distribution of planktonic foraminifera of sediment core SH1972_13. 21 records from Table 1. Location, water depth, grain size distribution, organic carbon and carbonate contents of the investigated Arctic and Antarctic surface sediment samples. 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 265 records from Geometry of coccolith Gephyrocapsa in sediment core K708-007. 12 records from Nannofossil abundance of Hole 74-528A. 5 records from Diatom abundance measured on water bottle samples at station PS58/043-2. 74 records from Description of a new Batrochoglanis species (Siluriformes, Pseudopimelodidae) from the rio Paraguai basin, State of Mato Grosso, Brazil.. 7531 records from UWBM Herpetology Collection (Arctos). 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 65 records from Planktic foraminifera counts of sediment core V29-219. 574015 records from LACM Vertebrate Collection. 5924 records from Colección de Radiolarios del Golfo de California, México (ICMyL-DF, UNAM). 15 records from Wasserbachsee. 1 records from Antarctic Marine Amoebae. 3165 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Santuario de Flora y Fauna Los Colorados. 374843 records from BSBI tetrad data for Ireland. 50 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part I. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 630 records from (Figure 3) Distribution chart of benthic foraminifers in ODP Site 126-790. 1534 records from Pontaurus. 435 records from (Table 4) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-654A. 378 records from (Table 2) Range chart of calcareous nannofossils in ODP Hole 122-762C. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 24 records from (Table 1) Distribution of calcareous nannofossils at ODP Hole 125-781A. 702 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 234 records from Sipuncula - SMF. 1617 records from (Table 7) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-714A. 431 records from Sistemática del género Polianthes L (Agavaceae). 4100 records from Actualización de la base de datos de crustáceos de la Colección Biológica de la Secretaría de Marina. 223881 records from UAM Entomology Collection (Arctos). 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 603 records from Collection of Industrial Microorganisms. 11300 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 510 records from University of Saskatchewan. 309941 records from Bryophytes of Ireland. 234 records from (Table 2) Selected planktonic foraminiferal species and other microfossil data for sedimentcore P69. 836 records from (Figure 4) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626D. 746 records from Assemblage of benthic foraminifera in sediment core GIK23414-8. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/565-1. 37 records from Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-976C. 950 records from (Appendix 2) Late Cretaceous benthic foraminifera of ODP Site 207-1259. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 420 records from (Table 3e) Foraminiferal distribution chart of petroleum well Leeuwin-1. 3189 records from Propuesta para la realización de 37 fichas biológicas de las especies de herpetofauna incluidas en la NOM-059 presentes en la Península de Yucatán. 565 records from Flora vascular del cerro El Zamorano. 307 records from Diversidad y distribución de las comunidades de peces de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 1240 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 478 records from Parásitos de peces nativos de cenotes de la Península de Yucatán, un ecosistema único en México. 507 records from Hongos hyphomycetes de áreas tropicales y semitropicales del Estado de Veracruz. 177 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 641 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 820 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 8470 records from (Table 12) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-714A. 414 records from (Table 1) Absolute abundance, diversity, and relative abundance of benthic Foraminifera species in Upper Pleistocene - Holocene bottom sediments from Core Vulk-34-98. 3641 records from Collection Ornithologie - SNSD. 36254 records from Fish collection of National Museum of Nature and Science. 4749 records from CNAC/Coleccion Nacional de Acaros. 1824 records from CNAN/Scorpiones. 1070 records from CNAN/Araneae. 46400 records from Museu Paraense Emilio Goeldi - Ophidia Collection. 60 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Steffen Matezki. 4 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Frank Haubrich. 61 records from Planktic foraminifera assemblage in sediment core GIK23074-3. 379 records from Planktic foraminifera assemblage in sediment core GIK17051-3. 11941 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 302 records from Stadtpark Sulzbach-Rosenberg. 269 records from 3. Tag der Artenvielfalt Hockenheim. 355 records from Tag der Artenvielfalt. 23 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 21 records from (Table 1) Dinoflagellate species and specimen abundance in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 24 records from Occurrence of mammalia relicts at site Kartstein. 74 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 62 records from Occurrence of mammalia relicts at site Pestera Livadita. 7789 records from Planktic foraminifera abundance of Hole 7-62A. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 1168 records from (Table 1) Relative abundance of 14 species of planktonic foraminifers of sediment core GIK17938-2. 43905 records from Herbarium of Jyväskylä University Museum. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 11009 records from IIAPPoa. 891 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core GIK12392-1. 806 records from Bulk components and planktonic foraminifera of sediment core GIK17748-2. 655171 records from Bugbase, Lepidopterological Society. 65344 records from UCM Amphibian and Reptile Collection (Arctos). 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 45 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB02 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 32 records from (Table 2) Planktonic foraminifer abundance of ODP Hole 162-907B. 12 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru. 2 records from Abundance of benthos infauna at station GIK23025-2. 46 records from Effects of varying food-availability on ecology and distribution of smallest benthic organisms in sediments of the arctic Fram Strait during POLARSTERN cruise ARK-XV/2. 763 records from Bisons Collection. 131 records from A contribution to the study of the Lower Volga center of scarab beetle diversity in Russia: checklist of the tribe Aphodiini (Coleoptera, Scarabaeidae) of Dosang environs. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 5759 records from EcoRecord - Mammal records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 6960 records from World flea collection of Slovenian Museum of Natural History (excluding Slovenia). 6943 records from DMNS Egg Collection (Arctos). 2 records from Coryphopterus kuna, a new goby (Perciformes: Gobiidae: Gobiinae) from the western Caribbean, with the identification of the late larval stage and an estimate of the pelagic larval duration.. 174617 records from Banc de dades de biodiversitat de Catalunya-VerteCat. 182864 records from Lepidoptera collection of Hannu Saarenmaa. 16007 records from NCOS1959_Mollusca (OBIS China). 1532 records from (Table A5) Distribution of planktic foraminifera and sea surface temperature reconstruction of sediment core V30-97 in the North Atlantic. 1051 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2040. 187 records from (Table Ib) Planktic foraminifera abundances in the earliest Paleocene sample interval of DSDP Hole 74-528 on the Walvish Ridge, South Atlantic. 80 records from Streuobstwiese/Naturerlebnisraum Koppelsberg (Plön). 13607 records from Fundación Miguel Lillo - Colección Ornitológica. 4 records from Occurrence of mammalia relicts at site Kobbelgard/Loc4. 64 records from Occurrence of mammalia relicts at site Spitalhöhle. 326 records from Neogene palynomorpha from site 81-555. 432 records from Planktic foraminifera abundance of Hole 22-216A. 5 records from Planktic foraminifera abundance of Hole 19-184B. 35 records from Planktic foraminifera abundance of Hole 67-499A. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 10 records from Range table from planktonic foraminifers in ODP Hole 182-1128D. 59 records from Benthic foraminifera abundance of Hole 34-320B. 790 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_100MC. 78 records from Rössewiesen am Krumbholz. 74734 records from Herbarium Senckenbergianum (FR). 2 records from Abundance of benthos infauna at station GIK23042-2. 12 records from Mean abundance Ophiocten gracilis and sediment surface area covered by the ophiuroids according to total diameter of individuals at different stations on Vøring Plateau. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 48 records from Planktic foraminifera abundance of Hole 47-397. 105 records from Planktic foraminifera abundance of Hole 18-181. 220 records from Foraminifera abundance of Hole 57-440. 28 records from Range table from planktonic foraminifers in ODP Hole 151-910D. 288 records from Range table from planktonic foraminifers in ODP Hole 154-929E. 470 records from (Table 7) Planktonic foraminifer abundance of ODP Hole 162-983A. 463 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 110 records from Range table from planktonic foraminifers in ODP Hole 182-1132C. 51 records from Benthic foraminifera abundance of Hole 42-380. 4051 records from Homoptera. 19 records from Dinoflagellate abundance of Hole 81-553A. 40 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1072A. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 71 records from tab3. 82 records from (Table 5) Planktonic foraminifera genera assemblage at DSDP Hole 80-548A. 249 records from (Table 3) Distribution of benthic foraminifers in middle Miocene sediments of ODP Hole 182-1126B in the Great Australian Bight. 489 records from ANTXXIII-8 Birds and Mammals (SCAR-MarBIN: Antarctic OBIS). 1 records from Abundance of benthos infauna at station GIK23065-1. 84 records from (Table 1) Occurrence of larger benthic foraminifers in ODP Hole 133-817D. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 6 records from (Table 1d) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the Late Neopleistocene - Holocene activity phase of the Keli Volcanic Highland. 10175 records from Seil Natural History Group - SNHG Biological Records Dataset. 6 records from (Figure 10) Occurrence of coccoliths in two carbonate cycles at DSDP Hole 71-511. 908 records from (Appendix A1) Planktonic foraminifera of ODP Hole 157-951A. 814 records from Biological Records Centre - Orthoptera and Allied Insects of the British Isles data from iRecord . 2252 records from Nijmegen Natural History Museum (NL) – Herbarium. 21912 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 6 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 92 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 2172 records from Coleccin de Reptiles. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 2080 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 8441 records from Natural England - Batsites inventory for England. 52 records from Fledermaus. 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 4 records from Neues Testprojekt. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 2511 records from (Table T5) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1052E. 5 records from (Table T5) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 2276 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 296 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rallidae. 731 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 1056927 records from Australian Museum provider for OZCAM. 794 records from Inventaire National du Patrimoine Naturel : CBN Alpin de Gap. 74 records from (Table T4) Paleocene calcareous nannofossil abundance of ODP Hole 173-1069A. 291402 records from ARABEL - Arachnologia Belgica. 434 records from (Table 4) Benthic foraminiferal community at DSDP Hole 94-609B. 4772 records from Butterflies of County Waterford. 485 records from National Taiwan Ocean University. 1 records from Zetes cespitum. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 632 records from MVZ Hildebrand Collection (Arctos). 12509 records from The Bat Conservation Trust - Hibernation Survey. 10000 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 105 records from BIRDRACE Kiesmätze. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 9589 records from (Appendix) Distribution of planktonic foraminifers at DSDP Hole 72-516F, Coniacian-Santonian to upper Maestrichtian. 133 records from Description of Haploblepharus kistnasamyi, a new catshark (Chondrichthyes: Scyliorhinidae) from South Africa.. 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 8748 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 77 records from Xiphosura collection of National Museum of Nature and Science. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 42861 records from DMNS Bird Collection (Arctos). 103 records from Mammalogie ZMK. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 385500 records from University of California Museum of Paleontology. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 64 records from Kabelskebach (Kabelsketal, Saalkreis). 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 29 records from Brenz (Heidenheim). 42 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 132 records from Plasm bearing foraminifera counts of multinet M21/1_MSN613. 73 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1196. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 1 records from Phytoplankton abundance at station Rigel_3_2005-08 in August 2005, Chipana, Chile. 12 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 39-356. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 461 records from Guadeloupe_Bananier. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 21091 records from NCSM Birds Collection. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 56 records from Estetal (Buxtehude). 51 records from Kindervilla Außengelände. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 169 records from Benthic foraminifera assemblage in sediment core BBLL2_MC1. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 55 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 63-125 µm fraction. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, 63-150 µm. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 10 records from Plasm bearing foraminifera counts from multinet M31/2_MSN891. 11 records from Foraminifera species abundances from tow TT011_2-MOC57. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 95 records from Birdrace-Buteo1_DO-Dortmund. 41 records from Örtzemündung (Stedden). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 28 records from Uferzone Wipper (Biesenrode). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 107 records from Müritz-Nationalpark. 97 records from BIRDRACE NABUhu Trier!. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 150 records from Total foraminifera counts of multinet M12/3_MSN533. 59 records from Total foraminifera counts of multinet M21/5_MSN739. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 107 records from Content of coarse fraction and G. menardii in sediment corev V26-102. 175 records from Abundance of planktic foraminifera at CTD station M39/4_361CTD-18. 306 records from Size of planktic foraminifera at CTD station PS55/037. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 23 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD39. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-20-5. 2241402 records from Biologiezentrum Linz. 11 records from Privatteich(St.Leon). 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 333 records from Distribution of calcareous foraminifers in sediment core Well 6407/7-2. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 9 records from Distribution of planktic foraminifera of sediment core GIK23352-3 at stadium 5.5. 239 records from Size of planktic foraminifera at CTD station M39/4_376CTD-29. 1 records from Oribates punctum. 5 records from Sarcodine counts and carbon biomass at station TT012_3-CTD5. 2 records from Pollen analysis of sediment profile SI0 from Siethener See. 6 records from Abundance of radiolaria at station UT99-20-1. 5 records from Tuttlinger Tag der Artenvielfalt. 100 records from Coccolith counts of multinet SO119_MSN1281. 18 records from Nannofossil abundance of Hole 64-481. 15902 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 2 records from Nannofossil abundance of Hole 74-526C. 279 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 20 records from Meiofauna abundance in sediment core 12930-029. 24 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI226. 39835 records from Lichen herbarium, Trondheim (TRH). 736 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 10570 records from Bumblebees, cuckoobees and butterflies in southern Poland. 6010 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during HEINCKE cruise HE133. 238 records from Ophion scutellaris species group specimen data. 152 records from Size of planktic foraminifera at CTD station M39/4_381CTD-34. 69 records from Faunal assemblage of sediment core GS7603-7. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 1 records from Microplankton counts and carbon biomass at station TT011_1-CTD4. 9 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/088-4. 10 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 86 records from Distribution of the sand-ascidian Seriocarpa rhizoides in surface sediments of Josephine-Bank, North Atlantic (Table 4). 4 records from Zwischen Enz und Schule. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 2 records from Nannofossil abundance of Hole 3-14. 2 records from Nannofossil abundance of Hole 9-82A. 24 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 33 records from (Appendix 2) Abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core SU81-18. 2084 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for sediment core R657. 197 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 105523 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 6149 records from Hongos del estado de Veracruz. 279 records from Herbarium of Lars Levi Laestadius. 25 records from Antarctic Krill occurrence data from Spanish RV "Fruela". 123 records from Pollen profile from Pittsburg Basin. 3 records from Nannofossil abundance of Hole 39-359A. 9 records from Diatom abundance measured on water bottle samples at station PS58/045-2. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 1381 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 4909 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 503 records from Dinoflagellate cysts from sediment core PS2138-1. 46003 records from Vascular plant specimens of Akita Prefectural Museum. 4 records from Reptilien und Insekten Entdecker / Schulgelände BBS Rotenburg. 9 records from Volkspark Prenzlauer Berg. 1 records from On the Chilopoda from Turkey. 801 records from Collection Porifera - ZMB. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 558 records from (Table 2) Relative abundance of selected benthic foraminifera in ODP Hole 104-642B. 290 records from Bacteria and chlorophyll-a water column observations (surface to ~150m), April-August 2001, Continental Margin Western Antarctic Peninsula, GLOBEC. 37 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-6. 149 records from Bayerische Donau - Neu Ulm. 4 records from Nannofossil abundance of Hole 29-281A. 46 records from Nannofossil abundance of Hole 26-254. 11 records from Diatom abundance measured on water bottle samples at station PS58/061-3. 903 records from (Table 2) Occurrence of ostracoda in surface sediments of the Arctic Ocean. 885 records from Asteroids from French subantarctic islands: records from the Marion Dufresne MD03 expeditions. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 3666 records from (Table 5) Stratigraphic ranges of selected Oligocene to earliest Miocene planktonic foraminifers in ODP Hole 115-709A. 26 records from (Table 4) Mean values of the chemical data from the ash layers from ODP Legs 113 and 114. 1627 records from Crustáceos estomatópodos, anfípodos, isópodos y decápodos del litoral de Quintana Roo. 356 records from An updated checklist of aquatic plants of Myanmar and Thailand. 333 records from Límites de especies dentro del género Gerrhonotus (Sauria: Anguidae). 222 records from Helmintos parásitos de peces de lagunas costeras de Jalisco, México. 3301 records from Relative abundances of dinoflagellate cysts in several IODP and DSDP holes. 46022 records from West African Vegetation Database. 32466 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2005) (AfrOBIS). 31082 records from MEXU/Plantas Vasculares. 632 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 105-645B. 317 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-714A. 124 records from (Table 5) Distribution of calcareous nannofossils in the Paleocene of ODP Hole 113-690C. 4 records from On the Chilopoda from Turkey. 5399 records from Lothian Wildlife Information Centre - Lothian Wildlife Information Centre Secret Garden Survey. 828 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV13. 364 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 28 records from (Table 2) Distribution of late Eocene calcareous nannofossils in ODP Hole 149-897C. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 944 records from Colección Mastozoológica de la Universidad Industrial de Santander. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 69959 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1998) (AfrOBIS). 67 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 638 records from Geochemistry and sedimentology on core PO200/10_21-1. 17 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM8. 1725 records from (Table 20) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-709A. 320 records from (Table 1) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-897A. 17369 records from MfN - Auchenorrhyncha Collection. 34253 records from MedOBIS (EurOBIS). 2586 records from Plant Specimens of Lake Biwa Museum. 1339 records from Percentages of planktonic foraminifera species in sediment core V25-75. 3 records from Analyses of the recent components of sediment core PS1010-1. 148 records from Hintere Halde. 1 records from Occurrence of mammalia relicts at site Polch. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 15 records from Planktic foraminifera abundance of Hole 1-6. 6 records from Type specimen data for Nicrophorus efferens Sikes & Mousseau. 20 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 2135 records from (Table 1) Distribution of benthic foraminifers at DSDP Site 90-590. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 498 records from Dinoflagellate abundance of Hole 94-611C. 526 records from FernsDarwinCore. 26 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto48-56. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 1 records from On two italian Lithobius species described by Silvestri with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda Lithobiidae). 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 12 records from Ohemoor (Hamburg/Norderstedt). 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 5449 records from Fishes in the Argentine Sea from 1967 to the present time (OBIS South America, SOUTHERN OCEAN SUB-NODE). 85519 records from TNHC Herpetology Collection. 10909 records from Utah Valley State College Herbarium. 13195 records from Fish Collection of Natural History Museum and Institute, Chiba. 39810 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 195 records from Sediment components of core SO82-4. 3139 records from Foraminifera and stable isotopes of sediment core PS2076-3. 4456 records from Colección de Artrópodos de la Asociación BIGA para el estudio del patrimonio natural de Galicia: ABIGA. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 940 records from Planktic foraminifera distribution of sediment core CS72-37. 5 records from Analyses of the recent components of sediment core PS1014-1. 325 records from (Table A.07) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (150-500 µm). 6782 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 156 records from Botanischer Garten (Saarbrücken). 132434 records from Field Museum of Natural History (Botany) Bryophyte Collection. 536 records from Walldorf-Wiesloch: "Natur über den Gleisen". 294 records from Naturgarten Langenholtensen. 17 records from (Table 2) Distribution of Manumiella seelandica in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 47 records from Occurrence of mammalia relicts at site l´Abri de Rhodes II. 4 records from Occurrence of mammalia relicts at site Seest. 6 records from Occurrence of mammalia relicts at site Magdalenhöhle. 32 records from Occurrence of mammalia relicts at site Jaskinia Niedwiedzia. 265 records from Planktic foraminifera abundance of Hole 73-521. 372 records from Agriculture and Agri-Food Canada, Saskatoon. 8 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 78 records from Occurrence of mammalia relicts at site Einhornhöhle. 373 records from Planktic foraminifera abundance of Hole 26-251. 51 records from Planktic foraminifera abundance of Hole 18-177. 817 records from Planktic foraminifera abundance of Hole 37-332A. 170 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 878 records from Planktic foraminifera abundance of Hole 84-568. 21 records from Range table from planktonic foraminifers in ODP Hole 172-1064A. 19 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 311 records from Range table from planktonic foraminifers in ODP Hole 192-1186A. 106 records from Benthic foraminifera abundance of Hole 32-308. 318 records from Gunma Museum of Natural History, Amphibia and Reptile Specimen. 130737 records from Ground Beetle Recording Scheme - Carabid data for Great Britain from the Ground Beetle Recording Scheme held by BRC. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 1968 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 85250 records from Green Plant Herbarium (TRT). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 92 records from Manx National Heritage - Odonata records from the Isle of Man. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 19127 records from Biological Records Centre - Cerambycidae Dataset. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 756 records from Targeting a portion of central European spider diversity for permanent preservation. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 2267 records from Relative abundance of organic-walled dinoflagellate cysts in surface sediments. 1347 records from (Table 16A) Occurrences of planktonic foraminifers in DSDP Hole 90-594, samples 594-1-CC through 594-30-CC. 27 records from Planktic foraminifera abundance of Hole 51-417B. 303 records from Planktic foraminifera abundance of Hole 94-608A. 109 records from Range table from planktonic foraminifers in ODP Hole 141-861D. 36351 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 31 records from Range table from planktonic foraminifers in ODP Hole 170-1042A. 4 records from Range table from planktonic foraminifers in ODP Hole 183-1137A. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 284968 records from Balfour-Browne Club - Water Beetle Surveys from Britain and Ireland. 1045806 records from Belgian IFBL Flora Checklists (1939-1971). 228 records from Phytoplankton abundance in surface water in June 1997, Pisco, Peru. 2355 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 1 records from Campylomorphus homalisinus (Elateridae): a new species for Lombardy (Italy), with notes on its ecology, distribution and biogeography. 1218925 records from Vascular Plants, Field notes, Oslo (O). 151334 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 9420 records from Sussex Biodiversity Record Centre - Sussex Bryophyte Atlas Data edited by Howard Matcham. 191 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s. l., Scelioninae). 3275 records from Quantitative Phytoplankton data from Irish lakes (EPA). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 33 records from Revision von Suctobelba trigona (Michael, 1888). 1 records from Zetes longiusculus. 1024 records from Benthic foraminiferal assemblages (living), surface data. 105 records from Dead benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 2016 records from (Table 1) Benthic foraminifer stratigraphy of ODP Site 166-1006 sediments. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 146 records from Colección de moldes endocraneanos del CENPAT. 29441 records from Animal Sound Archive. 114 records from RSPB - Tree sparrow recovery project â summary data, North West England, 2004-2010 (RSPB, NE, Wirral Borough Council, Cumbria Biodiversity Partnership). 1101354 records from Botany (UPS). 1 records from Il popolamento dell'Appennino meridionale: dall'Appennino campano alle serre calabre. Osservazioni sui chilopodi dell'Appennino lucano e calabrese (Chilopoda). 12 records from The African species of the subfamily Penestominae (Araneae: Eresidae): with descriptions of two new species. 13631 records from Beetles (LSM). 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 50 records from Description of Notarius biffi n. sp. and redescription of N. insculptus (Jordan and Gilbert) (Siluriformes: Ariidae) from the eastern Pacific, with evidence of monophyly and limits of Notarius.. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 10 records from Bachpatenschaft Beeke. 220 records from Total foraminifera counts of multinet SO118_MSN1253. 1575 records from Porifera MZS. 12 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/4 (ANDEEP II). 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 1665 records from Colección Ictiológica de la Universidad Industrial de Santander. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 35 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 200913 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 27299 records from NCSM Vertebrate Paleontology Collection. 88 records from Birdrace-WeserEggeLäufer-Höxter. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1054. 9 records from Microzooplankton abundance and biomass at station TT054_21-14. 6 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 133 records from Phytoplankton abundance at station CD46_2005C#4. 7 records from Distribution of meiobenthos in sediment core M23_133 of the northeastern Atlantic (Table 1). 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 2599 records from (Table A1) Ostracoda abundances in sediment core GIK23414-9. 280 records from Planktic foraminifera counts of sediment core RC11-126. 1932 records from Benthic and planktonic foraminifera in ODP Hole 123-766A (Table 1-4). 142 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE3. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 1733 records from Birds collection of Abiko City Museum of Birds. 1900 records from Fungi Collection. 43 records from Saalewiesen Naumburg. 28 records from Stadtpark Prinzengarten (Sigmaringen). 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 135 records from Waldi-Weiher. 111 records from BIRDRACE Die Wendehälse. 104 records from BIRDRACE Andechser Stativträger. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 1087 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 18 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, >125 µm fraction. 128 records from Total foraminifera counts from multinet M31/2_MSN895. 148 records from Total foraminifera counts from multinet SO119_MSN1278. 186 records from Total foraminifera counts from multinet SO119_MSN1283. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 200 records from Plasm bearing foraminifera counts from M35/1_MSN1070. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 299586 records from SEAPOP NINA. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 1914 records from Macrophytes_CLF. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 881 records from Moluscos Marinhos de Augusto Nobre. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 16006 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 74 records from Schulwald Grundschule Brügge. 140 records from BIRDRACE Guckers Offenbach. 172 records from Total foraminifera counts of multinet SO118_MSN1266. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 89 records from Total foraminifera counts of multinet M10/2_MSN298. 143 records from Total foraminifera counts of multinet M21/3_MSN674. 211 records from Total foraminifera counts of multinet M21/1_MSN610. 137 records from Total foraminifera counts of multinet M21/1_MSN603. 373 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 3 records from Biological Records Centre - ALERT Non-Native Species Records for Signal Crayfish. 169 records from Planktic foraminifera counts at CTD station PS55/051. 150 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 8 records from Microplankton counts and carbon biomass at station TT008_5-CTD25. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-14-13. 108 records from Plasm bearing foraminifera counts from M35/1_MSN1065. 9 records from (Table B) Abundance of benthic fauna associated with shrimp swarms at hydrothermal fields on the Mid-Atlantic Ridge. 140 records from Dinoflagellate cysts counted on two fractions of surface sediment samples from stations A-9 to A-39. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 20 records from (Table T2) Dinoflagellate cyst occurrence in neogene sediments of ODP Hole 178-1096C. 611 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/092-3. 11250 records from El Censo Neotropical de Aves Acuáticas en Colombia (CNAA): 2002 - 2011. 12 records from Distribution of meiobenthos in sediment core M19_229-2 of the northeastern Atlantic (Table 1). 322 records from Nannofossil abundance of Hole 15-147. 35 records from Nannofossil abundance of Hole 78-543. 2 records from Smear slide investigation on ODP Hole 205-1254A. 85 records from RSPB - Black grouse lek survey in Ross-shire. 1675 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 12 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-1. 36 records from Pollen profile ADR309. 337366 records from British Lichen Society - BLS Lichen Database: England. 49 records from Total foraminifera counts of multinet M10/2_MSN234. 57 records from Total foraminifera counts of multinet M21/4_MSN718. 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 27 records from Planktic foraminifera of sediment core GeoB1405-5. 172 records from Planktic foraminifera counts at CTD station PS55/081-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 14 records from Phytoplankton abundance in surface water in 1994, Ancon, Peru. 65 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 14 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 51 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 9 records from Numbers and dry weight of main macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 3). 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 12 records from Abundance of radiolaria at station LV28-44-1. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 864 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_5-CTD56. 6 records from Two new dolichoderine ant genera from Madagascar: Aptinoma gen. n. and Ravavy gen. n. (Hymenoptera: Formicidae).. 12 records from Nannofossil abundance of Hole 31-299. 4 records from Nannofossil abundance of Hole 60-454A. 110 records from (Table A.10) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (150-500 µm). 34 records from Relative abundance of coccosphere-units of sediment core GIK23071-3. 9 records from Nannofossil abundance of Hole 15-150. 125 records from (Appendix) Benthic foraminiferal abundance at DSDP Hole 71-511. 2 records from Nannofossil abundance of Hole 10-86. 4 records from Ostracoda abundance of Hole 32-305. 5 records from Phytoplankton abundance at station Casma_2003-06-04_1, Casma, Peru. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-059. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 1638 records from (Table 1) Relative abundances of benthonic foraminifera in ODP Site 116-717. 536 records from (Table 1) Absolute abundances of benthic foraminifera in ODP Site 120-747. 1298 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 45 records from BIRDRACE Ohne Graureiher läuft nix!. 88 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 114357 records from Data on moths from automatically operating light traps in Denmark. 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 48 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE218. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 380 records from Stable oxygen and carbon isotope ratios of Globigerinoides obliquus of quantitative range chart of the ostracodes in the Pliocene-Pleistocene interval of ODP Hole 107-654A. 32356 records from Actualización de la base de datos del Atlas Mastozoológico de México. 52 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 7 records from Nannofossil abundance of Hole 67-494. 33 records from Nannofossil abundance of Hole 73-522. 2 records from Range table from nannofossils in ODP Hole 139-855A. 374 records from Ratios of juvenile to total ostracode fauna in surface sediment samples from the Persian Gulf (Table 1b). 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/587-1. 4 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 130 records from Planktic foraminifera counts of sediment core RC11-120. 2349 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 163259 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 1139 records from Shellfish (MNHM-MS). 609 records from Herbier L. Mulon (BOUM). 650 records from (Figure 3) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-635B. 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 128 records from (Table 5) Distribution of the large, many-chambered Globigerinelloides species in the Calabianca section. 240 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part I. 4858 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Berkshire Meadows Survey 1984-87 (as held by Thames Valley Environmental Records Centre). 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 12077 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 702 records from Factual Database of Native Flora Seeds in Korea. 111529 records from The AAU Herbarium Database. 9754 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 195 records from Visual Plants (144.41.33.158) - Private collection of Eberhard Fischer. 12113 records from Distribution of planktic foraminifers and SST of sediment core GIK15637-1. 219 records from Prophetensee Quickborn. 167 records from (Table 6) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-601. 18 records from Range table from benthic foraminifers in ODP Hole 144-871A. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 45 records from NSG Dellwiger Wald, Dortmund. 1342350 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 19544 records from Collection Thysanoptera SMF. 159 records from (Table 1) Distribution of benthic foraminifera in surface sediment of the Elbe estuary. 27264 records from Formidabel; Belgian Ants Database. 216 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 39 records from Red list project inventory, fungi. 661414 records from Phanerogamic Botanical Collections (S). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 29587 records from EPA River Biologists data. 25874 records from Museu Paraense Emilio Goeldi - Ictiology Collection. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 1752 records from Herbier National de Mauritanie (HNM). 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 7 records from Pollen profile III at Krumbach. 103 records from Pollen analysis of Site 175-1075 (part 1). 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 2639 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 1818 records from Pliocene benthic foraminiferal abundances of ODP Hole 105-646B from north Atlantic. 3136 records from (Table 6) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-906A. 164915 records from Vascular Plant Collection. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 6348 records from South Western Pacific Regional OBIS Data Bryozoan Subset (South Western Paci fic OBIS). 651 records from Distribution of planktic foraminifera in sediment core GIK23071-5. 441 records from Planktic foraminifera distribution of sediment core 75KS76. 2 records from Occurrence of mammalia relicts at site Condover. 39 records from Occurrence of mammalia relicts at site la Grotte Maldidier. 98 records from (Figure 6k and 6l) Nannofossil accumulation rate and absolute abundances of coccoliths from ODP Site 1233. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 26 records from Occurrence of mammalia relicts at site Predmosti. 389 records from Planktic foraminifera abundance of Hole 23-228. 378 records from Planktic foraminifera abundance of Hole 68-503B. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 39 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-861C. 91451 records from Collection Mammalia SMF. 1924 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 97 records from CNIN/Tipos Hymenoptera. 318 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 168 records from (Table 1) Distribution of planktonic foraminifera species in Core ML2_66. 4830 records from (Table 5) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-905A. 26721 records from Bird Observational Records. 11574 records from Botanical Information System of Geneva. 23836 records from Korea Bird Distribution Atlas Database. 5 records from Memorial University Botanical Garden Collection. 2016 records from Fish tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 287 records from Freshwater fish Specimens of Taga Town Museum, Shiga Pref., Japan. 1135 records from Rare marine fishes taken in Irish waters from 1786 to 2008. 585 records from Foraminifera abundance of sediment core MD81-LC03. 63364 records from CCAMLR historic KRILL. 1161 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 154 records from Wildkräuter. 210 records from Lebensraum Gesamtschule (Langerwehe). 3 records from Casuarinicola australis Taylor, 2010 (Hemiptera: Triozidae), newly recorded from New Zealand. 53 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 1355 records from Planktic foraminifera abundance of Hole 18-173. 108 records from Planktic foraminifera abundance of Hole 27-263. 80 records from Planktic foraminifera abundance of Hole 49-409. 19 records from Range table from planktonic foraminifers in ODP Hole 139-858C. 192 records from Range table from planktonic foraminifers in ODP Hole 146-891B. 275 records from Benthic foraminifera abundance of Hole 84-566. 309 records from Range table from benthic foraminifers in ODP Hole 144-878A. 10 records from Content of different diatom species in sediment core GIK23259-2. 6 records from Oberservation of birds at station PS14/146 along 49° West. 7 records from Kaulsdorf. 202194 records from Tulane University Museum of Natural History. 1534 records from PonTaurus collection. 2054 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of DSDP Hole 38-338. 1752 records from (Table 3) Benthic foraminifera in early-middle Miocene sediments of DSDP Site 89-586. 9266 records from Naturhistorisches Museum Mainz, Paleontological Collection. 2588 records from A comparison of benthic biodiversity in the North Sea, English Channel and Celtic Seas (EurOBIS). 1004 records from Arctic soft-sediment macrobenthos (EurOBIS). 4500 records from Paranaguá Bay - Plankton and Benthos Database (OBIS South America, BRAZIL). 1098 records from Mushroom in North Korean (KIDR-MR). 115365 records from TTU Mammals Collection. 6627 records from ATCC Fungi Collection Catalog. 9902 records from DSMZ Bacteria. 704 records from DSMZ Collection on Plant Cell Cultures. 2911 records from Distribution of foraminifera of sediment core GeoB1112-4. 6602 records from Relative abundance of planktic foraminifera in sediment core GeoB1309-2. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1016-1. 341 records from (Table A.06) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (125-250 µm). 530 records from Nemertina World Checklist. 149 records from Trockenhang Greinhartsberg Edelfingen. 145 records from NSG Nollig. 602 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 14 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 14 records from Occurrence of mammalia relicts at site Petnicka Pecina. 990 records from Distribution of major planktic foraminifer at Site 177-1091. 182 records from Planktic foraminifera abundance of Hole 28-264A. 14 records from Range table from planktonic foraminifers in ODP Hole 143-865B. 196 records from Range table from planktonic foraminifers in ODP Hole 162-986D. 157 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera of surface sediment off Morocco (Table 6). 118309 records from Therevid PEET Project. 34958 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 1188 records from Countryside Council for Wales - Squirrel Collation for Wales. 1781 records from Soft Wheat French National Collection. 16866 records from Gravel Master Thesis / Chubut, Argentina. 1 records from Nothrus echinatus. 1102 records from Plantas laguna El Tinije. 221 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 185 records from Microbial Culture Collection, National Institute for Environmental Studies. 1 records from A new species of Crematogaster from the pinelands of the southeastern United States.. 49 records from A catalogue of the ants of Paraguay (Hymenoptera: Formicidae).. 58327 records from Inventaire National du Patrimoine Naturel : Fichier communal des ongulés. 1053 records from (Supplementary Table 1) Species abundance of benthic foraminifera (size fraction 150-500 µm) in sediment core GeoB11185-1. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 854 records from (Table T1) Abundance of stratigraphically important planktonic foraminifera in ODP Site 186-1150 sediments. 42 records from Pseudecheneis suppaetula, a new species of glyptosternine catfish (Teleostei: Sisoridae) from India.. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 58475 records from Oregon State University Herpetological Collection. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 223245 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 1445 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments. 1229 records from IITA Cameroon Insect. 740 records from (Table T15) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P6b-P8. 534 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 5426 records from Collection Francaise de Bacteries Phytopathogenes. 191802 records from Australian National Insect Collection. 1516 records from Coleoptera of Kozienice Forest. 286 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 3857 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Odonata Records up to Dec 2012. 26943 records from Collections of Phytoplankton at BGBM. 4567 records from Herbarium WRSL, Main Collection. 44561 records from Flora of the Stołowe Mts.. 1238 records from Insect Collection (CeStuBio). 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 2338 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 51148 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 8862 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 131642 records from mel. 153 records from Selztal bei Friesenheim. 5 records from Schulinnenhöfe (Gelsenkirchen). 369 records from BIRDRACE Havelland. 37641 records from Nordic Genetic Resources. 1 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 36657 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 1429 records from Herbier du Muséum Henri-Lecoq de Clermont-Ferrand - Rosacées. 355 records from CréBeo Earthworm Records 2006/7. 798 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 4852611 records from Bird Ringing Centre in Sweden (NRM). 2 records from Neue Milbenarten aus Kärnten. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000 . 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 1284 records from Collection of Heteroptera. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust, . 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 14420 records from Colección Nacional de Foraminíferos - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 96 records from BIRDRACE Emslandracer. 102 records from BIRDRACE Willi goes Birding. 38 records from Was lebt in der Brutzwiese?. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 2253 records from Irish National Crayfish Database. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 779 records from Harvestmen_of_French_Guiana. 6774 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 40697 records from Mammals housed at MHNG, Geneva. 92 records from Birdrace-Team_BO-bachter-Bochum. 43 records from Schulgelände Thurmair-Gymnasium. 39 records from Regenrückhaltebecken Bad Bevensen. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 12 records from Art´n Vielfalt im Kinderwald. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 119 records from Total foraminifera counts from multinet M31/2_MSN892. 115 records from Total foraminifera counts of multinet M33/1_MSN1028. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 50 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1338. 12 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5110-4. 34 records from Diatom assamblage in samples from sediment trap OG3. 10 records from Concentration of siliceous microplankton in surface sediments, size fraction > 40 µm. 29 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 12613 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD85. 6 records from Abundance of radiolaria at station UT99-4-2. 21 records from Nannofossil abundance of Hole 19-192. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 4 records from (Table 2) Maastrichtian calcareous nannofossils in DSDP Hole 22-217. 132 records from (Table 1) Distribution of microfossils in the Barrow Group of ODP Hole 122-762C. 107 records from (Table 12) Distribution of planktonic foraminifera shells with different preservation in deposits from DSDP Hole 30-289. 1789 records from Computarización de la Colección de Microorganismos de importancia acuícola del CIAD, AC. 2501 records from Helmintos parásitos de peces del sureste de México. 2 records from Description of lithologic section units of IODP Hole 325-M0049A. 70213 records from Coleção de Abelhas do Departamento de Biologia - FFCLRP/USP. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 57 records from (Figure 5) Foraminifera abundance and sea-surface temperature of sediment core JM97-948/2A. 35 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 15 records from Occurrence of mammalia relicts at site Dendermonde. 50 records from Planktic foraminifera abundance of Hole 60-457. 50 records from Range table from planktonic foraminifers in ODP Hole 169-1038I. 743 records from Fish monitoring data in Lake Kasumigaura. 2464 records from Benthic foraminiferal abundances at the Cretaceous/Paleogene boundary of ODP Hole 117-1049C at Blake Nose, Northwest Atlantic (Appendix A). 2233 records from Chrysomelidae of Poland. 65 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_4-CTD45. 30 records from Phytoplankton abundance in surface water in 2001, Ancon, Peru. 10 records from Phytoplankton abundance at station Rigel_4_2005-02 in Febraury 2005, Chipana, Chile. 5 records from Distribution of meiobenthos in sediment core M19_234-2 of the northeastern Atlantic (Table 1). 25 records from Coccosphere-units of site GIK23414. 45 records from Nannofossil abundance of Hole 64-481A. 4 records from Nannofossil abundance of Hole 3-16. 29 records from Nannofossil abundance of Hole 29-282. 6 records from Nannofossil abundance of Hole 94-610B. 51 records from Nannofossil abundance in sediment core PS1291-4. 48 records from Abundance of phytoplankton in surface water during THALASSA campaign PROSOPE. 7245 records from (Figure 5) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-627B. 582 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 3. 8523 records from Distribution of planktic foraminifers of core RC24-16. 204 records from Trockenrasen und Buchenwald in der Umgebung der Jugendherberge Bad Blankenburg. 8 records from Occurrence of mammalia relicts at site Wretton. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 8 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 91 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 132 records from Total foraminifera counts of multinet M10/2_MSN315. 159 records from Total foraminifera counts of multinet M21/6_MSN789. 132 records from Total foraminifera counts of multinet PO231/3_MSN1331. 129 records from Total foraminifera counts of multinet PO247/2_MSN1378. 265 records from Size of planktic foraminifera at CTD station PS55/084-1. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 133 records from Abundance of Bitectatodinium spongium in surface sediments. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD18. 3 records from Sarcodine counts and carbon biomass at station TT007_12-CTD145. 3 records from (Table T2) Dinoflagellate cyst occurrence in neogene sediments of ODP Hole 178-1096B. 5 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 21 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 431 records from (Table 6) Benthic foraminiferal community at DSDP Hole 94-611C. 24958 records from CABI Bioscience Genetic Resource Collection. 72391 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1997) (AfrOBIS). 7 records from (Table 3+4) Abundance, biomass, production, and grazing of prokaryotes, nanoflagellates, ciliates, and dinoflagellates in three areas close to the Antarctic Peninsula in spring and summer 1995/96. 11 records from Benthic macrofauna abundance of sediment core 13077-098. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 109 records from (Table 4) Meiofauna abundance in surface sediments of Cape Fear. 16 records from Seawater carbonate chemistry and processes during experiments with benthic foraminifera Ammonia tepida. 110 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD3. 1404 records from (Figure 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 93-603B. 1152 records from (Table 1) Occurrence of Oligocene to Pleistocene benthic foraminifers in ODP Hole 121-754A. 286 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C. 243 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B. 248 records from (Appendix 1d) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of ODP Hole 160-964A. 36 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 19386 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 1559 records from Plathelminthes - SMF. 3312 records from Base de datos sobre ictioplancton para la Bahía de Campeche, México. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 153 records from annex1. 193 records from Geometry of coccolith Coccolithus pelagicus in sediment core GIK23065-3. 2 records from Ostracoda abundance of Hole 13-129A. 7 records from Nannofossil abundance of Hole 7-64. 11 records from Nannofossil abundance of Hole 9-83. 42 records from Ostracoda abundance of Hole 48-406. 115 records from Nannofossil abundance of Hole 29-279A. 3 records from Nannofossil abundance of Hole 7-64. 57245 records from Bird Observation Data. 346 records from Packer Collection /Madagascar. 85 records from (Table I) Vital effect adjusted stable oxygen isotope ratios of Quaternary nannoplankton in DSDP Hole 90-593 from the Challenger Plateau, South Tasman Sea. 75 records from Macrofauna abundance in surface sediment sampled during cruise DI231. 4 records from Estimated plankton abundance at station PS63/064-6. 724 records from Planktic foraminifera counts of sediment core V29-64. 6 records from Bayerische Donau - Metten. 2020 records from Birds (NHMK-BI). 1603 records from Fossil (MNHM-FO). 1498 records from Biogeographic distribution of Antarctic and sub-Antarctic Cumacea. 106 records from Antarctic Nemertea. 1148 records from Southern Ocean Ostracoda (except Halocypridina). 98 records from (Table 10) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-664A. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 6414 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. ECOSUR_SNIB. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 940 records from Mastofauna de la vertiente occidental (oeste) del Parque Nacional Pico de Orizaba, Puebla (Fase 1). 22183 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 1453 records from Distribución e inventario de algunas especies bentónicas (hexacorales, octocorales, esponjas, y especies misceláneas) en arrecifes del Caribe mexicano. 24 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577. 2 records from Description of lithologic section units of IODP Hole 325-M0054A. 116 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 2656 records from Swiss Psyllid (Hemiptera) Collections - Basel. 2095 records from The SERTC Invertebrate Database: Invertebrates of the southeastern United States. 399 records from CECT Spanish Type Culture Collection(Fungi). 1131 records from (Appendix A1) Abundances of planktonic and benthic foraminifera in the Turonian to Coniacian sediments of ODP Site 207-1259. 414 records from Naturschutzstation Schmidsfelden. 226 records from Himmelmoor. 33 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB05 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 20 records from Occurrence of mammalia relicts at site Felslindlhöhle. 182 records from Planktic foraminifera abundance of Hole 62-465. 149 records from Planktic foraminifera abundance of Hole 29-282. 297 records from Foraminifera abundance of Hole 60-454A. 80 records from Planktic foraminifera abundance of Hole 49-411A. 105 records from Range table from planktonic foraminifers in ODP Hole 167-1016A. 569 records from Benthic foraminifera abundance of Hole 84-567A, Part 2. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 1385 records from Countryside Council for Wales - Amphibian & Reptile Licence Return Data . 12 records from Pseudanapis hoeferi, n. sp. from Central Amazonia, Brazil (Araneae, Anapidae).. 3015 records from Bird specimens in Gifu Prefectural Museum. 173 records from Sediment components of core SO82-2. 169 records from Planktic foraminifera assemblage in sediment core GIK23071-2. 613 records from Percentages of planktonic foraminifera species in sediment core V30-51. 261 records from Planktic foraminifera distribution of sediment core TRI171-24. 123 records from 4. GEO-Tag in Eberbach. 48 records from Deutsche Schule Budapest. 31229 records from DIPOL. 25 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 106 records from Occurrence of mammalia relicts at site l´Abri de la Madeleine. 10 records from Planktic foraminifera abundance of Hole 4-26. 230 records from Planktic foraminifera abundance of Hole 84-569. 114 records from Planktic foraminifera abundance of Hole 18-179. 10 records from Planktic foraminifera abundance of Hole 15-154A. 50 records from Planktic foraminifera abundance of Hole 11-106. 81 records from (Tab. 11) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-304, Japanese Magnetic Lineations east of Japan. 20273 records from Colección de Anfibios del Instituto Alexander von Humboldt. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 2. 15 records from Oberservation of birds at station PS14/159 along 49° West. 300 records from Gunma Museum of Natural History, Fish Specimen. 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 9136 records from “Endemic Species Research Institute Moth Survey” Dataset. 13 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 429 records from Range table from planktonic foraminifers in ODP Hole 182-1130A. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 775 records from (Fig. 16) Distribution of dinoflagellate cysts in Early Cretaceous sediments of ODP Hole 103-638C in the North Atlantic. 666 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-908A. 57350 records from Colorado State University Herbarium. 195 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 63 records from Museu Paraense Emilio Goeldi - Ricinulei Collection. 25592 records from Herbarium Amazonense. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 792 records from (Table 13) Benthic foraminifera in early-mid Miocene sediments of DSDP Hole 90-592. 2116 records from Collection entomologique Pierre Lachiver. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 365 records from Colección Herpetológica de la Patagonia. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 32109 records from Herbier de Nouvelle-Calédonie. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 59 records from Schulteich Freie Waldorfschule Darmstadt. 98 records from BIRDRACE Die Paradiesvögel. 112 records from BIRDRACE Gütersloher Gimpel. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 34 records from Total foraminifera counts of multinet M21/4_MSN717. 4662 records from The Mammal Society - National Mammal Atlas Project, online recording. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 7 records from Microplankton counts and carbon biomass at station TT008_5-CTD5. 403 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001F. 50 records from Range table from benthic foraminifers in ODP Hole 174-1071F. 3 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 38020 records from Vascular plants collection of Hiratsuka City Museum. 17 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (2000m section). 8 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 2046 records from (Table T3) Benthic foraminfera stratigraphy of ODP Hole 199-1221C sediments. 1273 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 48 records from (Appendix) Abundance of Discoaster brouweri and Coccolithus pelagicus in ODP Site 180-1115 sediments. 5344 records from Highland Biological Recording Group - HBRG Other Invertebrates Dataset. 21 records from (Table 8) Pleistocene nannofossil range chart for ODP Hole 134-833A. 13 records from Cresswell Associates - Wildlife Surveys in Southern Scotland 2007-2011. 1 records from Contributions a la faune Myriapodologiwue Mediterraneenne. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007 . 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 60 records from Total foraminifera counts of multinet FCA97C_MSN1344. 51 records from (Table III) Abundance of crustacea orders during RSS James Clark Ross cruise JR144. 116 records from Relative abundance of live benthic foraminifera of sediment core M5/2_98MC. 4 records from Abundance of benthos infauna at station GIK23017-1. 189 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE7. 2 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 724 records from Heritage Trees of Ireland. 63872 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 3201 records from Weevils of the Carpathians. 26 records from Akysis longifilis, a new species of catfish (Teleostei: Akysidae) from Myanmar.. 4 records from Four new species of deep-water catsharks of the genus Parmaturus (Carcharhiniformes: Scyliorhinidae) from New Caledonia, Indonesia and Australia.. 3253 records from Bryoquel : Spécimens de bryophytes de l'herbier de la Société Québécoise de Bryologie. 150 records from Isotope age and relative abundance of planktonic foraminifera in Core Vulk-34-90, Sea of Okhotsk. 5 records from Chenopodium vulvaria. 6663 records from Biological Records Centre - Pseudoscorpion Recording Scheme of the UK. 99 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 183 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 336 records from (Table T1) Calcareous nannofossil abundance estimates of ODP Hole 210-1276A.. 5589 records from Herbarium specimens of CBNA (GAP). 333 records from Phytoplankton measured on water bottle samples during THALASSA cruise PROSOPE. 78 records from Aktion - Friedensburg Oberschule. 2730 records from (Table AT5) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130A. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 84 records from (Table 3) Minerals, and calcareous and siliceous fossil residues from DSDP Hole 93-603. 1 records from Miriapodi di alcune grotte della Campania. 11 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Diomedeidae. 49 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 60 records from (Fig. 5) Distribution of Chironomids of sediment core Lz1103 from Duck Lake. 19 records from Two sympatric species of Antrodiaetus from southwestern North Carolina (Araneae, Mygalomorphae, Antrodiaetidae). 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad) . 471 records from Aschelminth collection of National Museum of Nature and Science. 2815 records from Helgeland Museum, Araneae. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1980519 records from Museum of Comparative Zoology, Harvard University. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 91 records from Birdrace-Enger_am_Spektiv-Herford. 79 records from Balkon (Norderstedt). 49 records from Dörnberg. 81 records from Schulgarten-St.-Georg-Gymnasium. 8 records from Krittenhorster Wald (Ostkilver). 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 177 records from BIRDRACE Mehr Seh Team. 110 records from BIRDRACE Linumer Luchschleicher. 5 records from (Table 2) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840A. 1 records from New species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Côte d’Ivoire. 94 records from (Table 2) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-198A. 15 records from A new species of Cynopotamus Valenciennes, 1849 (Characiformes, Characidae) with a key to the species of the genus.. 6 records from Pollen profile RAA37, Lake Racou, France. 103 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thamnophilidae. 24 records from From Corsica to Britain: new outdoor records of Ocnerodrilidae (Annelida: Clitellata) in western Europe. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 6179 records from Southern Cape herbarium. 2258 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 1196 records from Entomological collection of the National Museum. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 13086 records from Collection of Coleoptera. 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 807 records from Reunion_Coffea. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 1915 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 122 records from Stever. 101 records from Isartal Dingolfing. 120 records from BIRDRACE Ornis im Einsatz. 49 records from Total foraminifera counts of multinet M10/2_MSN268. 74 records from Total foraminifera counts of multinet M21/4_MSN699. 742 records from Paleogene dinoflagellates from Thyra-O-Formation, eastern North Greenland. 9 records from Microzooplankton abundance and biomass at station TT043_2-1. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 36 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 121 records from (Table 2, 3) Macro- and meiofaunal specimens abundance, organic carbon content and analysis of coarse clasts of box core samples from the North Pacific Ocean. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 85975 records from Mollusca specimens of Toyama Science Museum. 170 records from Benthic macrofauna abundance of subcores of sediment core 12930-065. 40 records from Macrofauna biomass in surface sediment sampled during cruise DI226. 72 records from Planktic foraminifera counts of sediment core V29-30. 7 records from A revision of the Aphaenogaster phalangium complex (Hymenoptera: Formicidae: Myrmicinae).. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 593 records from Ostracoda in sediment core PS51/159-10. 917 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 45 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-09. 89 records from Assemblage of living benthic foraminifera in sediment core GeoB4918-4. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1045. 128 records from Plasm bearing foraminifera counts of multinet M21/5_MSN740. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 6 records from Microzooplankton abundance and biomass at station TT043_7-20. 5 records from Sarcodine counts and carbon biomass at station TT012_5-TM69. 126 records from Mol·luscs d'Andorra. 783 records from Phytoplankton abundance in surface water during cruise CD61. 145 records from Phytoplankton abundance at station CD46_0405C#7. 5 records from Phytoplankton abundance at station Rigel_6_2005-08 in August 2005, Chipana, Chile. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 46 records from Aktion Wiese und Wegrain Gitzenheide. 62 records from Abundance of coccosphere-units of sediment core GIK23400-3. 9 records from Coccolith counts of multinet M32/5_MSN982. 51 records from Coccoliths in sediment core PS1295-4. 2 records from Nannofossil abundance of Hole 1-5. 17 records from Nannofossil abundance of Hole 3-13. 120 records from Nannofossil abundance of Hole 47-397. 15 records from Microfossil abundance of Hole 59-450. 88 records from Nannofossil abundance of Hole 40-362. 41 records from Liether Park (LMS), 6c. 52 records from Total foraminifera counts of multinet M21/4_MSN713. 81 records from Total foraminifera counts of multinet M21/5_MSN728. 21 records from Foraminifera species abundances from tow TT007_15-MOC23. 62 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/553-11. 125 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 2 records from (Fig. 5) Pollen analysis of the Furo do Chato core. 10 records from Microzooplankton abundance and biomass at station TT045_26-3. 1 records from Microzooplankton abundance and biomass at station TT050_2-10. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 3 records from Sarcodine counts and carbon biomass at station TT007_15-CTD160. 1 records from Hoplophora lucida. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 13 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 5 records from Phytoplankton abundance at station Casma_2003-06-24_2, Casma, Peru. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 33 records from Coccolith counts of multinet M32/5_MSN977. 56 records from Ostracod species in Oligocene sediments of core CRP-2A. 52 records from Nanoplankton abundance at station GeoB2017-4. 56 records from Nanoplankton abundance at station GeoB2021-3. 2 records from Nannofossil abundance of Hole 6-58. 3 records from Nannofossil abundance of Hole 37-333A. 30 records from Nannofossil abundance of Hole 94-608. 26 records from Phytoplankton abundance duringG. O. Sars cruise GS90/6. 6 records from Ostracoda abundance of Hole 13-134. 352 records from Ostracoda abundance of Hole 95-612. 2 records from Nannofossil abundance of Hole 9-79A. 5 records from Nannofossil abundance of Hole 77-536. 4 records from Nannofossil abundance of Hole 52-418. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 22 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 94 records from Collection Bryozoa - ZMB. 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 360 records from (Figure 6) Range chart of planktonic foraminifers across the K/T boundary at ODP Hole 120-750A. 22 records from Geophagus abalios, G. dicrozoster and G. winemilleri (Perciformes: Cichlidae), three new species from Venezuela.. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 370 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-710A. 1427 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 1351 records from Pteridoflora de Morelos. 107 records from Bases de datos de Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 650 records from Relative abundance of planktic foraminifera in sediment core K708-001. 14 records from Nannofossil abundance of Hole 94-611A. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/593-3. 9 records from Benthic macrofauna abundance of sediment core 13200-025. 254 records from Grünes Germersheim. 27828 records from svalbardflora.net. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 40 records from Pollen record of sediment core Bokanjacko Blato 1. 2109 records from Helmintos de peces dulceacuícolas de México. 2008 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 326 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 8577 records from Base de datos sobre la flora de Durango. 12772 records from UAM Invertebrate Collection (Arctos). 2427 records from Ibaraki Nature Museum, Mollusk collection. 2128 records from (Table 14) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-716B. 310 records from (Table S1) Dinoflagellate cysts, pollen and spores of sediment core ABC26. 7 records from (Table 4) Concentrations of PCBs and MeSO2-PCBs in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 477 records from Biodamaz1. 73 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ben Hell. 976457 records from EURISCO, The European Genetic Resources Search Catalogue. 792 records from Geochemistry and sedimentology on core PO200/10_28-1. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 255 records from Planktic foraminifera counts of sediment core RC09-150. 921 records from Planktic foraminifera counts of sediment core RC14-37. 315 records from Planktic foraminifera counts of sediment core RC17-69. 1192 records from (Table 1) Relative abundances of benthic foraminifera in ODP Hole 117-725C. 638 records from MNA - Sezione di Genova - (Marine Biological Samples). 64 records from Lissarca notorcadensis. 36 records from Collection Cnidaria - ZSM München. 105 records from (Table 2) Components of turbidite samples of ODP Leg 101 holes. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 246 records from Repatriación del material ictiológico de 12 estados de la República Mexicana, depositado en la colección ictiológica de la Universidad de Tulane, E.U.. 1201 records from Computarización de las Colecciones de Anfibios y Reptiles del Centro de Investigaciones Biológicas de la Universidad Autónoma del Estado de Hidalgo. 4529 records from Flora Novo Galiciana-Gramineae. 2940 records from RSPB - Cirl bunting national surveys in the UK (SCARABBS). 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 4 records from (Table 1) Biomass of cysts and active infusoria in the surface layer of the Central Indian Ocean. 1620 records from (Figure 5) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-513. 7535 records from Marine and Coastal Management - Demersal Surveys (years 1983-1985) (AfrOBIS). 4770 records from Peter Hall Observations. 19628 records from Bryophytes Collection of National Museum of Nature and Science. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 162 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano. 1431 records from (Table 10) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-712A. 2374 records from DSMZ Collection of Filamentous Fungi and Yeasts. 1028827 records from SEAMAP - marine mammals, birds and turtles. 1214 records from BioMar (EurOBIS). 74164 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2000) (AfrOBIS). 334 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 84571 records from Repatriación de datos del Herbario de Arizona (ARIZ). 2330 records from (Appendix C) Distribution of benthic foraminifera in surface sediments from the Chatham Rise. 68 records from Occurrence of mammalia relicts at site l´Abri du Morin. 29520 records from (Table T2) Foraminifer distribution in ODP Site 188-1165 sediments. 9 records from Radiolaria assemblage in sediment core GIK23411-5. 1626 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 1275 records from Range table from planktonic foraminifers in ODP Hole 155-931B. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 48 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 111 records from (Table 5) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2138-1. 2109 records from Harvestmen (Opiliones) of Ireland. 189 records from Naturpark Sternberger Seenland. 2 records from Apectodinium spp. and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 182-1128D. 18 records from (Table 3) Distribution of middle Eocene calcareous nannofossils in ODP Hole 149-897C. 7490 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Trawl. 37240 records from LSUMZ Mammals Collection. 51 records from Sea Algae. 1520 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-38. 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 49 records from Schaalbach. 238 records from Umgebung der Gesamtschule Winterhude (Hamburg). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 1050 records from (Table 6) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583F. 253 records from Planktic foraminifera abundance of Hole 24-233. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 251 records from Benthic foraminifera abundance of Hole 80-549A. 66 records from Sedimentology and radiolarian distribution in latest Miocene to Recent sediments of ODP Site 75-532 from the Benguela Upwelling System, South Atlantic. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 11098 records from Herbario de Universidad de Murcia: MUB. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 28 records from Plant - Plant Virus (KIDR-PL). 259408 records from MSB Mammal Collection (Arctos). 392 records from Relative abundances of planktonic foraminifera from surface sediments of the Drake Passage, Southern Ocean (Table 1). 41 records from Altholzparzelle Eilenriede Hannover. 235 records from katzenbuckel. 44 records from Leegmoor (Moormerland/Leer). 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MAY-1995-D4. 181 records from Occurrence of mammalia relicts at site Kemathenhöhle. 46 records from Palynomorph data and remarks on dominant tree taxa from IODP Hole 313-M0028A. 3 records from Occurrence of mammalia relicts at site Sesselfelsgrotte. 1 records from Planktic foraminifera abundance of Hole 8-74. 186 records from Planktic foraminifera abundance of Hole 26-255. 372 records from Planktic foraminifera abundance of Hole 73-523. 203 records from Foraminifera abundance of Hole 48-404. 85 records from Range table from planktonic foraminifers in ODP Hole 151-909C. 121 records from Range table from planktonic foraminifers in ODP Hole 167-1011B. 194 records from Range table from planktonic foraminifers in ODP Hole 182-1128C. 127 records from Benthic foraminifera abundance of Hole 95-613. 381 records from Range table from benthic foraminifers in ODP Hole 198-1212A. 103 records from Range table from benthic foraminifers in ODP Hole 139-855C. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 268 records from Range table from benthic foraminifers in ODP Hole 159-959A. 102 records from Microfossil abundance of Hole 39-354. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 2318 records from Fundación Miguel Lillo - Colección Ictiológica. 13 records from (Table 5) Distribution of calcareous nannofossil species at DSDP Hole 40-361. 3 records from Analyses of the recent components of sediment core PS1403-1. 1 records from Arthropoden aus südostalpinen Höhlen.. 3329 records from Universitat de València, Colecciones de Criptógamas: VAL_Briof. 17155 records from MZFC/Coleccion de Aves. 88 records from Countryside Council for Wales - Great Crested Newt SAC Monitoring Data. 1003 records from BÜG. 465 records from Philosophenwald und Wieseckaue in Gießen. 1036 records from BUND - Dassower See (Lübeck/Dassow). 376 records from Wupperaue bei Kemna (Wuppertal). 77 records from Occurrence of mammalia relicts at site Remetehegy. 278 records from Planktic foraminifera abundance of Hole 39-354. 778 records from Planktic foraminifera abundance of Hole 40-362. 111 records from Planktic foraminifera abundance of Hole 36-329. 182790 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 226 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 2 records from Benthic foraminifera abundance of Hole 42-374. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 710 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 107473 records from Botany Division, Yale Peabody Museum. 28648 records from The DNA and Sample Repository at AIT. 34 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM4. 1145 records from Colección de Anélidos. 13 records from Environment Agency - Environment Agency white-clawed crayfish Survey of the River Lune Catchment 2004. 6 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 2928 records from (Figure 11) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-538A. 53209 records from SysTax - Herbaria. 49362 records from Yorkshire Wildlife Trust - Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 25128 records from Royal Museum of Central Africa - Albertian Rift Butterflies (ENBI wp13). 1 records from Waldtag in und um Seelingstädt. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 1 records from Joseph F. Rock Herbarium. 109452 records from Biological Records Centre - Cranefly (Diptera; Tipuloidea) records for Britain to 2007. 4 records from A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar.. 49 records from Museu Paraense Emilio Goeldi - Uropygi Collection. 1236 records from Coleoptera of Biebrza National Park. 84 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 5195 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Types. 763412 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 631 records from RSPB - 2008 Twite (Carduelis flavirostris) Breeding Season Survey, Wales RSPB/CCW. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 31216 records from MSB Bird Collection (Arctos). 8913 records from Wilson Botanical Garden - Las Cruces Biological Station. 24 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 545 records from (Table T2) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1209A, Shatsky Rise, Pacific Ocean. 4400 records from USAC Mammals Collection. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 4501 records from Colección de Mamíferos del Centro Nacional Patagónico. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 374 records from published_chenopodium_vulvaria_observations. 545 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 4 records from A new species of Tychobythinus Ganglbauer, 1896 (Coleoptera: Staphylinidae: Pselaphinae) from Turkey. 38 records from Northern Ireland European hare (Lepus europaeus) survey 2005. 20824 records from Carabidae of the Carpathians. 8 records from (Table 1) Proportion of Toxoplasma gondii seropositive arctic foxes (Alopex lagopus) by age group and geographic area. 99749 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 106428 records from Jordal. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 92 records from Birkenloh. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 274 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction >150 µm. 107 records from Total foraminifera counts of multinet PO247/2_MSN1390. 137 records from Planktic foraminifera counts at CTD station PS55/077-1. 342 records from Size of planktic foraminifera at CTD station PS55/025. 16 records from Smear slide analysis on sediment core GeoB4223-2. 328 records from Range table from planktonic foraminifers in ODP Hole 170-1040C. 31 records from A revision of the gobiid fish genus Trypauchen (Gobiidae: Amblyopinae).. 3582 records from UCMC_Entomology. 174 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 306-U1313. 75 records from (Table S1c) Measured tomographic parameters for Nuttallides truempyi during the PETM for ODP Site 208-1263. 5962 records from Broadland Environmental Services Limited - Reptile distribution within Broadland (2004-2011): based upon field signs and sightings. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 45159 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 9248 records from UAM Fish Collection (Arctos). 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011 . 88693 records from Ichthyology Collection - Royal Ontario Museum. 201485 records from CAS Ichthyology (ICH). 99 records from Dorfrand Mauderode. 27 records from Zwickau- Schwanenteich. 10 records from schlittschuhweiher. 93 records from Haarbach Höfe. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 23 records from Plasm bearing foraminifera counts from multinet M32/3_MSN958. 76 records from Total foraminifera counts of multinet M21/4_MSN724. 122 records from Total foraminifera counts of multinet M21/2_MSN639. 1834 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Mariposas. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 538 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 153532169 records from EOD - eBird Observation Dataset. 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 117 records from Wassermann. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 77 records from VFD-RP: Taunus: Mähweide Dehe. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 75 records from Faunal assemblage of sediment core GS7603-9. 147 records from Total foraminifera counts from multinet M31/2_MSN889. 94 records from Total foraminifera counts from M35/1_MSN1074. 7621 records from Bryophyte collection of Porto Herbarium (PO). 122 records from Total foraminifera counts of multinet M21/2_MSN651. 123 records from Total foraminifera counts of multinet PO247/2_MSN1376. 248 records from Orca observations from the shores of Macquarie Island. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 2 records from Cnidaria ZMK. 688 records from Algae, Norwegian College of Fishery Science. 6821 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 59 records from Oschenberg, NO von Bayreuth-Laineck. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 238 records from Total foraminifera counts from multinet M31/3_MSN913. 107 records from Total foraminifera counts of multinet M10/2_MSN334. 3 records from A new species of whiptail stingray of the genus Dasyatis Rafinesque, 1810 from the Southwestern Atlantic Ocean (Chondrichthyes: Myliobatiformes: Dasyatidae).. 53 records from Total foraminifera counts of multinet M21/4_MSN702. 54 records from Total foraminifera counts of multinet M21/4_MSN707. 154 records from Total foraminifera counts of multinet M36/6_MSN1197. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 88 records from Total foraminifera counts of multinet PO247/2_MSN1384. 110 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1377. 18 records from Content of coarse fraction and G. menardii in sediment corev V25-57. 1 records from Microplankton counts and carbon biomass at station TT007_12-CTD145. 37 records from Phytoplankton abundance at bottle station GOM4/1. 10 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 56 records from Microzooplankton abundance measured on water bottle samples at station PS58/041-2. 11 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 84 records from (Table 4) Morphologic variability in the Globorotalia puncticulata group and abundances of dominant species at DSDP Hole 80-548. 137 records from Abundance of planktic foraminifera at CTD station PS55/019. 24 records from Counts (2) of calcareous dinocysts along profile Stevns-Klint. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_33-4. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_9-CTD113. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD20. 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 22 records from Phytoplankton abundance at bottle station GOM6/1. 4 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 322 records from Faunal assemblage of ODP Hole 101-633A (Table 2). 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 2 records from Nannofossil abundance of Hole 58-442. 16 records from Nannofossil abundance of Hole 24-236. 61 records from Nannofossil abundance in sediment core PS1294-4. 2 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 14 records from Benthic macrofauna abundance of sediment core 12930-028. 1368 records from Bird Collection of Yokosuka City Museum. 741 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 6 records from Folklore and Natural History Museum Mammal. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 15 records from Phytoplankton abundance at station Rigel_3_2005-04 in April 2005, Chipana, Chile. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-039. 316 records from Planktic foraminifera counts of sediment core RC11-86. 138 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE236. 72 records from (Table 1) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-682A. 2220 records from (Figure 9) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-633A. 1464 records from Inventario ficoflorístico de las comunidades arrecifales del Parque Nacional Bahías de Huatulco, Oaxaca. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 14842 records from Real Jardin Botanico, Madrid: MA-Lichen. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 13570 records from Royal Botanical Gardens Herbarium. 77258 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 789 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 102 records from Dinocyst assemblages of site HM52-43. 22 records from Planktic foraminifera abundance of Hole 6-48B. 150 records from Planktic foraminifera abundance of Hole 31-299. 10234 records from Collection entomologique Barthélémy. 8 records from Mean values of fractionated primary production and protozoan abundance from the photic layer collected at 50 m depth in Mejillones Bay. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 7 records from Distribution of meiobenthos in sediment core M23_199 of the northeastern Atlantic (Table 1). 73 records from Pollen profile from Seminary School Basin. 43 records from MfN - Fossil invertebrates Ib. 20942 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 8 records from Diatom abundance measured on water bottle samples at station PS58/091-4. 1513 records from A geographic distribution database of Mononychellus mites (Acari: Tetranychidae) on cassava (Manihot esculenta). 2779 records from Museu Paraense Emílio Goeldi - Herbarium Fanerógama Collection. 20672 records from MSB Parasite Collection (Arctos). 213 records from Planktic foraminifera counts of sediment core RC11-121. 48 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE275. 85 records from (Fig. 10g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD99-2339. 23 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-110BX. 122 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 128 records from Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 172-1055B. 92061 records from Herbarium (ICEL). 69 records from Coccolith counts of multinet SO119_MSN1295. 411 records from Coccolith percentage of surface sediment samples. 39 records from RIKEN BioResource Center, Experimental Animal Division. 2 records from Nannofossil abundance of Hole 34-321. 11 records from Nannofossil abundance of Hole 6-56B. 4 records from Nannofossil abundance of Hole 29-284A. 16 records from Nannofossil abundance of Hole 37-332B. 9 records from Nannofossil abundance of Hole 26-250. 27 records from Ostracoda abundance of Hole 34-320B. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 647 records from Planktic foraminifera counts of sediment core V29-172. 1180 records from Planktic foraminifera counts of sediment core V29-174. 26896 records from Vascular plants database of Atugi City Museum. 61 records from BIRDRACE Kollektiv Eisente. 2 records from Atlaszeder in Oma´s Garten. 5995 records from Insect (HUNM-IN). 3968 records from Antarctic Jellyfish. 3062 records from Collection Polychaeta - ZIM Hamburg. 88 records from (Table 4) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-658A. 27 records from (Table 9) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-663A. 11 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 115 records from (Table 2) Abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 124 records from Pollen profile from Samerberg 2. 3538 records from Anfibios del Estado de Veracruz.. 4 records from Arthropoden aus südostalpinen Höhlen.. 69 records from (Table 7) Distribution of Maestrichtian to late Campanian nannofossils in ODP Hole 108-661A. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 40 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE272. 1 records from Pollen record of profile L11. 40 records from Revisión de las categorías en el proyecto de norma oficial mexicana (PROY-NOM-059-2000) para las especies de lagartijas de la familia Anguidae (Reptilia). 1016 records from Diversidad de los coleópteros Scarabaeiodea del estado de Puebla (II). 858 records from Diversidad y distribución de las comunidades de fitoplancton de ríos y lagunas del volcán San Martín de la reserva de la biósfera Los Tuxtlas. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 500 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 270 records from (Table 2) Distribution of planktonic foraminiferal species in bottom sediments from Core LV28-42-5, Sea of Okhotsk. 144 records from Endocast Collection -CONICET- Argentina. 5549 records from National Survey on Odonata. 215389 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 4288 records from Universitat de Girona: HGI-Cormophyta. 12445 records from Museo Nacional de Ciencias Naturales, Madrid. Colección de Tejidos y ADN. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 30985 records from MEXU/Asteraceae. 17 records from Visual Plants (144.41.33.158) - Private collection of Vindas Jorge, Costa Rica. 834 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core A180-073. 194 records from (Table 2) Sea surface temperature reconstruction from sediment core MD88-770. 54 records from Range table from planktonic foraminifers in ODP Hole 141-862A. 46 records from (Table 1) Distribution of planktic foraminifera in sediments from Core AMK4-410GC. 1241 records from (Appendix 2, Part 2) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-689. 21795 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 1854 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 21076 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Lepidóptera. 7311 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 17982 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 15709 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 45841 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2004) (AfrOBIS). 9208 records from AWI-Herbarium Marine Macroalgae. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 177 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 57 records from Planktic foraminifera assemblage in sediment core GIK23055-2. 2197 records from Benthic foraminifera distribution of sediment core BP00-07/05. 248 records from Innenstadt Göttingen - Natur Zuhause. 12 records from Microplankton abundance at bottle station SEPT-1999-K2. 157 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 9 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB4. 484 records from Foraminifera abundance of Hole 74-529. 100 records from Birdrace-Meister_der_Herzen-Kleve. 180 records from Paul-Gerhardt-Schule Dassel. 520 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 21 records from Typhlomyrmex meire, a remarkable new species endemic to Southern Bahia, Brazil (Formicidae: Ectatomminae).. 6 records from Sediment properties of core CD86_11_BC8. 171 records from Foraminifera abundance of sediment core C1960.201. 272 records from Foraminifera distribution of sediment core LynchII-3. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 7 records from Analyses of the recent components of sediment core PS1222-1. 257 records from Kernberge und Umgebung (Jena). 224 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 11371 records from Mammal specimens. 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 10 records from (Table A) Abundance of species detected in mussel beds within hydrothermal fields on the Mid-Atlantic Ridge. 12 records from Occurrence of mammalia relicts at site Trafalgar Square. 10 records from Occurrence of mammalia relicts at site Pekarna. 6 records from Occurrence of mammalia relicts at site Mitoc Malul Galben. 68 records from Occurrence of mammalia relicts at site Schweizerbild. 28 records from Foraminifera abundance of Hole 86-580. 207 records from Foraminifera abundance of Hole 58-444. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 525 records from Planktic foraminifera abundance of Hole 94-609. 1592 records from (Table 8) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-584. 1420 records from Planktic foraminifera abundance of Hole 49-407. 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 233 records from Range table from planktonic foraminifers in ODP Hole 180-1115B. 15 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0003A. 1444 records from Benthic foraminifera and algae abundance of Hole 95-612. 84 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 2 records from Range table from benthic foraminifers in ODP Hole 178-1100D. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 67 records from Range table from nannofossils in ODP Hole 199-1217A. 4 records from Dinoflagellate abundance of Hole 81-554A. 39 records from Dinoflagellate abundance of Hole 94-607A. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 561 records from EDIT - ATBI in Borjomi/Kharagauli (Georgia). 2737 records from Gunma Museum of Natural History, Molluscan Specimen. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 17035 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 22999 records from Shire Group of Internal Drainage Boards - Shire Group IDB species data 2004 to present. 76 records from (Table T1) Distribution of selected calcareous nannofossils at the Paleocene/Eocene boundary, ODP Hole 208-1266C. 3027 records from Fungi Collection in BCRC. 25727 records from Irish National Badger Sett Database. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 8159 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 3780 records from Distribution of benthic foraminifers (dead) in surface sediments (Table 5). 533 records from Range table from benthic foraminifers in ODP Hole 175-1076A. 836 records from Distribution of Upper Cretaceous deep water agglutinated foraminifera in sediments of the North Atlantic and its marginal seas (Tab. 1). 14 records from Microfossil abundance of Hole 29-277. 168 records from Phytoplankton abundance in surface water in September 1996, Callao, Peru. 26 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Buchaugraben in the Lower Inn Valley area. 12 records from Oberservation of birds at station PS14/158 along 49° West. 1 records from Carabodes coriaceus. 34140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 21 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (2000m section). 14522 records from MVZ Egg and Nest Collection (Arctos). 20 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto20-28. 32 records from Revision of the genus Sinopoda Jäger, 1999 in Laos with discovery of the first eyeless huntsman spider species (Sparassidae: Heteropodinae). 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 5 records from (Table T9) Calcareous nannofossil stratigraphy of ODP Hole 198-1211C. 4176 records from Badger and Habitats Survey of Ireland. 347524 records from National Forest Inventory (SLU). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 27191 records from Collection of saproxylic and xylobiont Beetles. 133 records from Range table from benthic foraminifers in ODP Hole 181-1122A. 258 records from Range table from benthic foraminifers in ODP Hole 144-877A. 7 records from Pollen and spore abundance of Hole 42-380A. 108 records from Phytoplankton abundance in surface water in October 1996, Paita, Peru. 1404 records from (Table 2) Distribution of benthic foraminifers in the > 125 µm fraction in surface sediments from the central Arctic Ocean. 40019 records from Carpatica Operation. 21 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 519 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 184 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 276 records from Entomological specimens of Museum fuer Naturkunde und Vorgeschichte Dessau. 198566 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 400 records from Colección Hidrobiológica del Chocó. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 798 records from Biological Records Centre - Irish Otter Dataset. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 6884 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 4 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 67978 records from CU Invertebrate Paleontology. 969 records from Coleoptera of Tuchola Forest and Tuchola Forest National Park. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 41698 records from Queen Victoria Museum Art Gallery provider for OZCAM. 55 records from Revisionary studies on the attine ant genus Trachymyrmex Forel. Part 3: The Jamaicensis group (Hymenoptera: Formicidae).. 67 records from (Table 2) Constituents of the sand-size fraction of ODP Site 139-857. 2465 records from Countryside Council for Wales - Bat Roosts Database - North West Wales. 3 records from Res Ligusticae XXII. Diagnosi di nuove specie di miriapodi cavernicoli. 27 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 1 records from Zetes dorsalis. 196 records from (Figure 4) Distribution of dinoflagellates in ODP Hole 129-802A. 9329 records from Centre de Ressources Biologiques de l'Institut Pasteur. 111 records from (Figure 3) Foraminiferal assemblages recovered from DSDP Hole 79-547B. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 314 records from Peces laguna El Tinije. 987 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thraupidae. 90 records from (Table 3) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-800A. 55816 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 149 records from Museu Paraense Emilio Goeldi - Amblypygi Collection. 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 3253 records from ISU Birds. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 9703 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 6936559 records from OEH Atlas of NSW Wildlife. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 2880 records from Coleoptera, NEF. 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 1364 records from Irish Collembola records. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 37986 records from rmca-albertine-rift-cichlids. 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 77 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria (Gastropoda). 22 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 5459 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 193 records from Gelände des Schulzentrums am Himmelsbarg. 21 records from Tauchen und Meer 02. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 134 records from BIRDRACE Griffin Wood Warblers. 115 records from BIRDRACE Die UHULOGEN. 790 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_100MC. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 82 records from Total foraminifera counts of multinet FCA97C_MSN1346. 131 records from Total foraminifera counts of multinet M21/6_MSN788. 48 records from Plasm bearing foraminifera counts of multinet M27/2_MSN882. 27 records from Total foraminifera counts of trap L3_92_45. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 28 records from Sandgrube Zaisertshofen. 13 records from Garten Hamburg Uhlenhorst. 81 records from Stadtpark Schmölln. 721 records from IBF Monitoring of Plant Galls. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 138 records from BIRDRACE Arkonauten. 149 records from BIRDRACE Birding Bentheim. 31 records from Düpenauwiesen. 7 records from Die Bachspezies. 30 records from Höhle am Neuweg / Sächsische Schweiz. 54 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 73 records from Faunal assemblage of sediment core GS7603-13. 222 records from Total foraminifera counts from multinet M31/3_MSN910. 31 records from Total foraminifera counts of multinet M10/2_MSN322. 170 records from Total foraminifera counts of multinet M21/3_MSN687. 251821 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 89 records from Birdrace-Team_Wangerooge-Friesland. 56 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 84 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1331. 7 records from Microplankton counts and carbon biomass at station TT012_5-CTD59. 12 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 27 records from Phytoplankton abundance at station Rigel_3_2005-05 in May 2005, Chipana, Chile. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 29 records from Coccolith counts of multinet SO119_MSN1301. 8 records from Nannofossil abundance of Hole 6-47. 1508 records from Spider (YCEM-SP). 29716 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 90 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE218. 11779 records from Ecología y biogeografía de epífitas vasculares de Chiapas, México. 43242 records from Bentos collection of the Museum of Nature and Human Activities, Hyogo. 30 records from (Table 6) Distribution of diatoms in Miocene to Pleistocene sediments of DSDP Hole 7-66. 31157 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2003) (AfrOBIS). 1657 records from Phragmites of Canada. 12844 records from Herbarium Faeroense. 2 records from Nothrus palustris. 1074258 records from invertebratezoology. 1684 records from MfN Fish Collection, Zoology. 113 records from Total foraminifera counts of multinet M21/2_MSN627. 102 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1380. 11 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5117-1. 110 records from Planktic foraminifera counts at CTD station M39/4_366CTD-22. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_9-CTD108. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-03-3. 118 records from Phytoplankton abundance at Station Sechin_EP2 in 2002, Casma, Peru. 11 records from Phytoplankton abundance at station Sechin_2003-10-03_1, Casma, Peru. 292 records from (Table A1) Calcareous nannofossil of the Middle Cenomanian Event in ODP Site 207-1260. 958 records from (Table 6) Planktonic foraminifera in ODP Holes 139-856A and 139-857A. 197 records from Coleoptera identified from the Horton Kirby site, near London. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 7139 records from Snow Petrel census, Reeve Hill, Windmill Island, East Antarctica (1984-2003). 319 records from Upper Aptian Pré-Guittard (Niveau Kilian) range chart in percentages of nannofossils in SE France. 55 records from Coccolith counts of multinet SO119_MSN1284. 5311 records from Gulf of Maine Bottom Trawl Survey Data (NEFSC,NMFS,NOAA)(USOBIS). 321 records from Calcareous dionoflagellate cysts from surface sediments. 1 records from Microplankton counts and carbon biomass at station TT011_10-CTD123. 3 records from Sarcodine counts and carbon biomass at station TT007_5-CTD53. 470 records from Phytoplankton abundance during Lev Titov cruise LT90/5. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 261 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Orthoptera Records up to Dec 2012. 1045745 records from Herbarium of The New York Botanical Garden. 446 records from Bayerische Donau - Blindheim Donaubrücke. 113 records from (Table 5) Ostracod assemblages of sediment core 9407. 28 records from Nannofossil abundance of Hole 4-26. 10 records from Ostracoda abundance of Hole 44-390. 19 records from Nannofossil abundance of Hole 36-329. 419 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 14 records from Benthic macrofauna abundance of sediment core 13077-089. 13 records from Benthic macrofauna abundance of sediment core 13200-008. 8345 records from Colección Nacional de Equinodermos Mexicanos (ICMyL-DF, UNAM). 3772 records from Fish (KIWE-PI). 45 records from Collection Bryozoa - ZIM Hamburg. 1497 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 180 records from (Table 1) Distribution of plaktonic foraminifers in ODP Hole 125-786A. 8 records from Component analysis of TV-guided grab sampler GeoB10071-4. 1265 records from (Table 16) Distribution of planktonic foraminifers in ODP Hole 108-667A. 127499 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 71 records from Nannofossil abundance of Hole 64-478. 128 records from Nannofossil abundance of Hole 4-25. 26 records from Ostracoda abundance of Hole 11-105. 25 records from Ostracoda abundance of Hole 34-320. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 16 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/012-5. 14 records from A review of the genus Mystrium (Hymenoptera: Formicidae) in the Indo-Australian region.. 44 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 201 records from Seawater carbonate chemistry and processes during experiments with coccolithophores (Emiliania huxleyi and Gephyrocapsa oceanica), 2000. 153 records from Dinoflagellate cysts from sediment core PS2471-1. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 3 records from Fledermauserlebnistag für Kinder am Laacher See. 99727 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 311 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 504759 records from Western Australian Museum provider for OZCAM. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-13. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 1293 records from Pliocene-Pleistocene distribution of benthic foraminifers from ODP Hole 110-672A (Table 2). 478 records from EASIANET. 53482 records from Herbarium (AMNH). 53 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE262. 84 records from Seawater carbonate chemistry and processes during experiments with phytoplankton Emiliania huxleyi (strain Bergen 2005), 2010. 21 records from (Table 3) Paleotemperature estimates for ODP Hole 105-646B. 9900 records from Museo Nacional de Ciencias Naturales. CSIC, Madrid: MNCN-Nemata. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 678 records from Ictiofauna de los ríos Papagayo, Atoyac y Coyuca. 11408 records from Molluscs of the Natural History Museum in Gothenburg. 1756 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 978 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 92 records from Los hongos silvestres: componentes de la biodiversidad y alternativa para la sustentabilidad de los bosques templados. 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 8089 records from Los díptera hematófagos y taxa relacionados de dos áreas protegidas del estado de Yucatán, México (Insecta). 11 records from Akita Prefectural Museum＋Ascidians Specimens of Akita Prefectural Museum. 64 records from Akita Prefectural Museum＋Echinoderms Specimens of Akita Prefectural Museum. 37963 records from Zoological collections of the University of Tartu. 22 records from Phythoplankton abundance measured on water bottle samples during POLARSTERN cruise ANT-X/6. 1092 records from (Table 5) Oligocene planktonic foraminifera of DSDP Hole 29-277. 45 records from Nekton and plankton counts from bongo net (300, 500 µm) hauls of cruise GAE 1975/76. 15663 records from Collection Herpetologie - SNSD. 24 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part II. 48 records from Pollen counts of sediment core GeoB9503-5. 5125 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 1659 records from Auchenorhyncha collections of SW Finland. 6723 records from NOAA HML Tidal Creek Database. 2883 records from Inventory of Antarctic seabird breeding sites. 6229 records from (Table 9) Percentages of planktonic foraminiferal taxa from Site GIK17940. 4 records from Pycnogonida collection of National Museum of Nature and Science. 424 records from Distribution of planktic foraminifera in sediment core GIK16397-2. 884 records from Percentages of planktonic foraminifera species in sediment core EN066-10PG. 1309 records from Benthic foraminifera distribution of sediment core BP01-62/06. 398 records from Mooswald (Freiburg). 249 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 81 records from GEO-Tag der Artenvielfalt auf dem Bausenberg mit den 4. Klassen der Brohltaler Grundschulen. 129 records from Occurrence of mammalia relicts at site Koziarna Cave. 4 records from Occurrence of mammalia relicts at site Henauhof NW 2. 749 records from Planktic foraminifera abundance of Hole 15-154A. 1 records from Planktic foraminifera abundance of Hole 28-274. 604 records from (Table 7) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583G. 7 records from Planktic foraminifera abundance of Hole 53-418B. 100 records from Birdrace-The_Ringers-Friesland. 84070 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1988) (AfrOBIS). 207 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 600 records from Bulk components, concentration and planktonic foraminifera of sediment core GeoB7112-5. 783 records from RAVON (NL) - Fish observations extracted from Hoek (1890) and Redeke (1921). 83 records from Frau Voss. 364 records from Langenberger Forst am Ochsenweg/ Niebüll-Leck. 115 records from Wismar Bucht coast-watching. 11 records from Microplankton abundance at bottle station SEPT-1999-K3. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB6. 50 records from Occurrence of mammalia relicts at site Sveduv stul. 3 records from Occurrence of mammalia relicts at site Conturines Höhle. 66 records from Abundance of radiolaria in surface sediment, Sea of Okhotsk. 1979 records from Planktic foraminifera abundance of Hole 72-518. 82 records from Planktic foraminifera abundance of Hole 14-144A. 78 records from Planktic foraminifera abundance of Hole 22-212. 148 records from Planktic foraminifera abundance of Hole 15-154. 57 records from Range table from planktonic foraminifers in ODP Hole 172-1056B. 17 records from Range table from planktonic foraminifers in ODP Hole 173-1069A. 1 records from Range table from planktonic foraminifers in ODP Hole 185-1149B. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 525 records from Benthic foraminifera abundance of Hole 40-360. 960 records from Benthic foraminifera and algae abundance of Hole 81-555. 528 records from Phytoplankton abundance in surface water in October 1997, Paita, Peru. 10 records from Occurrence data of Mydidae from the southern Arabian Peninsula (Diptera: Asiloidea). 1 records from Pelops auritus. 3562 records from Lepidoptera specimen database of Osaka Museum of Natural History. 1368 records from Distribution of planktic foraminifers of core Y71-06-12. 138 records from Birdrace_MarschPIeper_Pinneberg. 30 records from A new species of Farlowella Eigenmann and Eigenmann (Siluriformes: Loricariidae), a stickcatfish from Bolivia.. 32 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 598 records from Foraminifera abundance of Hole 60-459B. 379 records from Planktic foraminifera abundance of Hole 49-412. 448 records from Range table from planktonic foraminifers in ODP Hole 160-967A. 122 records from Range table from planktonic foraminifers in ODP Hole 170-1041A. 1 records from Range table from planktonic foraminifers in ODP Hole 172-1062H. 269 records from Range table from planktonic foraminifers in ODP Hole 182-1126C. 8 records from Benthic foraminifera abundance of Hole 96-622. 8 records from Range table from benthic foraminifers in ODP Hole 188-1165C. 1 records from Pollen and spore abundance of Hole 42-381. 3 records from Observation of birds at station PS14/153 along 49° West. 293 records from EPOS3: SeaStars (Echinodermata, Asteroidea). 794 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 21 records from RSPB - Twite, winter distribution in Caithness and Sutherland 2006/7. 2 records from Abundance of benthos infauna at station GIK23071-1. 4290 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2009. 45308 records from Biological Records Centre - Water Bug (aquatic Heteroptera) data for Britain . 6 records from Una nuova specie di Eupolybothrus della fauna di Grecia (Chilopoda, Lithobiomorpha). 3 records from Mammalia (SMNH-MM). 2107 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 124 records from Range table from planktonic foraminifers in ODP Hole 171-1052B. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1095D. 11 records from Range table from planktonic foraminifers in ODP Hole 182-1129A. 432 records from Range table from benthic foraminifers in ODP Hole 172-1057B. 404 records from Range table from benthic foraminifers in ODP Hole 189-1171D. 68 records from Range table from benthic foraminifers in ODP Hole 149-897C. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 615 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from Microfossil abundance of Hole 35-323. 540 records from Phytoplankton abundance in surface water in September 1997, Ilo, Peru. 96423 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Invertebrate Observation Records other than Lepidoptera. Pre-2010 for Cumbria . 854 records from CIRM-Levures. 82 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ciconiidae. 29367 records from Geographic distribution of dinoflagellate cysts in surface sediments. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 1524 records from (Appendix A2) Planktonic foraminifera and microfossil occurence in ODP Hole 130-806B. 46710 records from Invertebrates of the Gothenburg Natural History Museum (GNM). 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 1 records from Die Gattung Carabodes C. L. Koch 1836 in der schwedischen Bodenfauna (Acar. Oribat.). 1050 records from Relativ abundances of total live fauna of benthic foraminifera in surface sediments (Table C1.1). 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 352271 records from New Mexico Biodiversity Collections Consortium database. 44 records from Flora und Fauna in unserer Kita. 11 records from Collection Xiphosura SMF. 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 18 records from Composition of benthic macrofauna in surface sediments of the east Greenland continental slope (79° N section). 7360 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 24 records from A new genus and two new species of congrid eels (Teleostei: Anguilliformes: Congridae) from the Indo-West Pacific, with a redescription and osteology of Chiloconger dentatus.. 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 1 records from Damaeus nodipes. 2467 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 219817 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 43 records from 12) SST, IRD and benthic foraminiferal d18O data from core EW9302-JPC2: revised chronology for the Last Interglacial (period 134-110 ka). 169086 records from Estonian Nature Observations Database. 1471 records from EcoRecord - Bryophyte records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 25486 records from Biological Records Centre - Opiliones (Harvestman) Dataset. 55 records from A taxonomic revision of the Pheidole roosevelti-group (Hymenoptera: Formicidae) in Fiji.. 62428 records from South East Wales Biodiversity Records Centre - Microlepidoptera of Glamorgan . 4555 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 767 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids, and associated organisms from DSDP Hole 77-536. 35748 records from Inventaire National du Patrimoine Naturel : Insectes Coléoptères Scarabéidés Laparostici de France. 63 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 627220 records from Naturalis Biodiversity Center (NL) - Mollusca. 2749 records from Miscellaneous Vascular Plants. 1 records from Arthropoden aus südostalpinen Höhlen.. 44206 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 1 records from Zetes ephippiatus. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 52 records from The high alpine bee fauna (Hymenoptera: Apoidea) of the Zillertal Alps, Austria. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 245 records from Gieselbachtal Fulda-Harmerz. 155 records from Bammentaler Duft- und Heilkräutergarten. 4 records from Sächsische Schweiz (Wehlener Gebiet). 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 32297 records from Invertebrata Collection of Institute of Systematics and Evolution of Animals. 1320 records from (Table T14) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P4a-P6a. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 253095 records from Lyman Entomological Museum (LEMQ). 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 1 records from Celaeno spinosa. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 97586 records from CAS Ornithology (ORN). 1 records from Zur Kenntnis der Lithobiiden. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 1 records from Graureiher in Lans. 144 records from BIRDRACE Die Mohrenlerchen. 329 records from Benthic foraminifera counts of sediment core GIK23351-1. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 26 records from Plasm bearing foraminifera counts from M35/1_MSN1052. 186 records from Total foraminifera counts of multinet M10/2_MSN218. 186 records from Schulhof Goethe-Gymnasium (Emmendingen). 311768 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 1 records from Hoplophora ferruginea. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Haematopodidae. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 24657 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 1419 records from Kangawalla Bird Sightings. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 2654 records from Collection of Hymenoptera. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 13389 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 40 records from Flächennaturdenkmal Grubditz. 61 records from BIRDRACE Baumläufer. 253 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23256-1 in the Arctic Ocean. 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 5438 records from (Appendix A) Benthic foraminiferal assemblages in sediments of the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 100 records from (Supplement Table 7) Globigerina bulloides concentration record of ODP Hole 117-723A, western Arabian Sea. 25 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5133-1. 2154 records from (Table T1) Census counts of planktic foraminifers at ODP Hole 175-1087A. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 137 records from Planktic foraminifera counts at CTD station PS55/019. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 16 records from Dinoflagellate cysts of sediments core IOW211660-6. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_838-1. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_7-CTD82. 29 records from Hemmerder Schelk (Unna). 19309 records from Mammal collection, Natural History Museum, University of Oslo. 150 records from Steinbruch Mainz-Weisenau. 22 records from Heilpflanzen im Hainbachtal. 87 records from Klütwald. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 1314 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 33 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, 63-125 µm fraction. 25 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC464. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD22. 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-03-7. 1408 records from Biosphärenpark Wienerwald - Pfaffstätten. 56 records from Lebensraum Walram. 51 records from Coccolith counts of multinet M32/5_MSN971. 2 records from Nannofossil abundance of Hole 1-1. 14 records from Nannofossil abundance of Hole 49-412. 29 records from Range table from ostracoda in ODP Hole 151-911A. 17 records from (Table 3) Nannofossil occurrence in the Albian of ODP Hole 101-635B. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 700 records from (Table 3c) Foraminiferal distribution chart of ODP Hole 122-762C. 114 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 43 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 82 records from Plasm bearing foraminifera counts of multinet M27/2_MSN883. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 35 records from Planktic foraminifera of sediment core GeoB1404-3. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 22 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 15 records from Phytoplankton abundance at station Sechin_2003-12-10_2, Casma, Peru. 244 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 10 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 74-525A. 140 records from Distribution of planktonic foraminifera of sediment core SH1972_17. 68 records from Nannofossil abundance of Hole 34-319. 8 records from Nannofossil abundance of Hole 28-266. 18 records from Nannofossil abundance of Hole 8-73. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 936 records from Bats of Poland. 78 records from Planktic foraminifera counts of sediment core A180-73. 53 records from Planktic foraminifera counts of sediment core ELT48.027-PC. 282 records from Planktic foraminifera counts of sediment core V19-201. 63 records from Planktic foraminifera counts of sediment core V19-21. 34 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 22419 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 124 records from Total foraminifera counts of multinet M21/1_MSN620. 348 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 79 records from Plasm bearing foraminifera counts of multinet M21/2_MSN628. 4 records from Microzooplankton abundance and biomass at station TT050_13-14. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_4-CTD8. 22 records from Phytoplankton abundance in surface water in January 2007, Sechura Bay, Peru. 2 records from Nannofossil abundance of Hole 10-87. 12 records from Nannofossil abundance of Hole 20-200. 60 records from Ostracoda abundance of Hole 48-405. 6 records from Nannofossil abundance of Hole 60-457. 4 records from Nannofossil abundance of Hole 3-17. 14 records from Nannofossil abundance of Hole 14-140. 21 records from Nannofossil abundance of Hole 24-232A. 55 records from Nannofossil abundance of Hole 94-609. 84 records from Planktic foraminifera counts of sediment core V22-188. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 121 records from Table II: Birds observed at the Weddell Sea during the period: 22 December 1959 to 14 January 1960. 3005 records from Annotated Atlas of the Vascular Flora of Macquarie Island - 1979. 110 records from Palynomorph concentrations in ODP Hole 105-645B samples (Table 1). 79 records from (Appendix E) Analyses of the benthic foraminifer assemblage at ODP Hole 112-681B. 757 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 510 records from Alterra (NL) - Microarthropods inventory in a range of forests. 6 records from Microzooplankton abundance and biomass at station NBP97-08-08-1. 14 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 12 records from Phytoplankton abundance at station Sechin_2003-09-18_2, Casma, Peru. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 20 records from Abundance of radiolaria at station LV28-4-1. 94 records from Nationalpark Jasmund. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 34 records from annex4. 83 records from Coccoliths in sediment core GIK23065-3. 36 records from Nannofossil abundance of Hole 37-333. 2 records from Nannofossil abundance of Hole 74-526. 8 records from Nannofossil abundance of Hole 49-412A. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 6 records from Abundance of two benthic foraminifera species in sediment core 12930-007. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI229. 159248 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 20338 records from Insect (JNHM-IN). 2702 records from (Appendix B) Abundance of benthic foraminifera in sediment cores GIK17964-3 and GIK17964-2. 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 4702 records from Amphibian specimens. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 19 records from (Table 1) Planktonic foraminifer abundance and stable isotope ratios of a sediment core near Baddeckenstedt, north Germany. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 3 records from Akita Prefectural Museum＋Millipedes Specimens of Akita Prefectural Museum. 7076556 records from Great Backyard Bird Count. 9810 records from Royal British Columbia Museum Entomology Collection. 364 records from Bird tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 83 records from Visual Plants (144.41.33.158) - Private collection of Juergen Homeier. 242 records from (Table 1) Planktonic foraminiferal abundance at DSDP Site 94-606. 669 records from Relative abundance of planktic foraminifera in sediment core SO136-011GC. 10733 records from Distribution of foraminifera of sediment core GIK23258-2. 44 records from Planktic foraminifera assemblage in sediment core GIK23256-1. 246 records from Rotifers of Macquarie Island. 61 records from Planktic foraminifera abundance of Hole 7-64A. 17485 records from DORSA - German Orthoptera Collections. 290 records from Foraminifera abundance of Hole 64-477. 6 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 535 records from Benthic foraminifera abundance of Hole 73-522. 112 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 455 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 106 records from Irish Wire Weed (Sargassum muticum) Database. 2 records from Neobythitoides serratus, a new bathyal genus and species from the East China Sea (Teleostei, Ophidiidae).. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 1 records from Damaeus auritus. 36079 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 2387 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 4 records from Description of lithologic section units of IODP Hole 325-M0052B. 363 records from Planktic foraminifera assemblage in sediment core GIK17730-4. 131 records from Unser Schulhof - eine Apotheke. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D2. 1 records from Occurrence of mammalia relicts at site High Furlong. 10 records from Planktic foraminifera abundance of Hole 14-140A. 4 records from Planktic foraminifera abundance of Hole 54-422. 813 records from Foraminifera abundance of Hole 64-479. 2087 records from Range table from planktonic foraminifers in ODP Hole 144-871A. 105 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 35 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 523 records from Range table from benthic foraminifers in ODP Hole 146-888B. 1099940 records from DOF 2001-2006. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 4450 records from Wildlife Sightings. 11964093 records from Tiira information service. 26 records from A new tarantula species from northern Australia (Araneae, Theraphosidae). 1 records from Nothrus gibbus. 1 records from Arthropoden aus südostalpinen Höhlen.. 400 records from Colección Limnológica del Chocó. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 86 records from Naturerlebnisraum Koppelsberg (Plön). 146 records from Total foraminifera counts of multinet PO200/6_MSN837. 1351 records from Collection Crustacea ZMG. 909 records from South American Antarctic Marine Biodiversity Literature. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 933 records from Flora de las Barrancas del Cobre. 20374 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 3 records from Akita Prefectural Museum＋Echiurans Specimens of Akita Prefectural Museum. 941 records from Pteridophyta specimens of Iwate Prefectural Museum. 21000 records from Akita Prefectural Museum:Observation Records of Birds in Akita Prefecture. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 13960 records from Collection Trichoptera - SMF. 43356 records from Canadian Museum of Nature Fish Collection. 9674 records from Mammal collection of National Museum of Nature and Science. 2291 records from Bird Collection. 193 records from Administración Nacional de Institutos y Laboratorios de Salud. 19903 records from HBGSpermatophyta - Herbarium Hamburgense. 690 records from DSMZ Collection of Plant Viruses. 2098 records from Distribution of planktic foraminifers of core V19-29. 750 records from Planktic foraminifera assemblage in sediment core SU90-I02. 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 80 records from Artenvielfalt auf Restbauernhof. 19 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB04 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1994-D4. 21 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 24 records from Occurrence of mammalia relicts at site Poroslyuk. 37 records from Occurrence of mammalia relicts at site Große Ofnethöhle. 15 records from Planktic foraminifera abundance of Hole 19-191. 14 records from Planktic foraminifera abundance of Hole 20-199. 49 records from Planktic foraminifera abundance of Hole 73-522A. 2 records from Nannofossil abundance of Hole 1-5. 1 records from Akita Prefectural Museum＋Specimens of Phylum Nemertea of Akita Prefectural Museum. 70 records from Korean Aquatic Vascular Plants. 4664 records from Database Schema for UC Davis [TGRC]. 40472 records from MEXU/Colección de Briofitas. 1000 records from Plant Specimens of Taga Town Museum, Shiga Pref., Japan. 763 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 289 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 438 records from Planktic foraminifera abundance of Hole 74-525A. 79 records from RSPB - Black grouse lek survey in Sutherland 2008-9 (RSPB). 6 records from Foraminifera abundance of Hole 58-442. 237 records from Planktic foraminifera abundance of Hole 32-305. 47 records from Planktic foraminifera abundance of Hole 72-515. 1 records from Range table from planktonic foraminifers in ODP Hole 139-856G. 190 records from Range table from planktonic foraminifers in ODP Hole 139-857C. 37 records from Range table from planktonic foraminifers in ODP Hole 172-1060A. 33 records from Benthic foraminifera abundance of Hole 76-533A. 8 records from Pollen and spore abundance of Hole 42-380. 511 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1170D. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 150 records from Phytoplankton abundance in surface water in October 1996, Pisco, Peru. 1998 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 359 records from Diversity of live benthic foraminiferal assemblages in South Atlantic surface sediments. 2324 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 430 records from Collection Strepsiptera SMF. 94 records from Landschaftsschutzgebiet Buchhorst 4. 241 records from Planktic foraminifera abundance of Hole 67-499B. 83 records from Range table from planktonic foraminifers in ODP Hole 139-858A. 3147 records from Range table from planktonic foraminifers in ODP Hole 159-959B. 193 records from (Table 10) Planktonic foraminifer abundance of ODP Site 162-986. 17 records from Range table from planktonic foraminifers in ODP Hole 172-1054B. 1824 records from (Fig. 5) Occurrences of selected planktonic foraminifers in samples from ODP Hole 184-1148A in the South China Sea. 43 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 108 records from Phytoplankton abundance off Guañape bay in Juli 2003, Peru. 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 2618 records from MEXU/Agavaceae. 165 records from Occurrence of the most important taxa of macrofauna on Voering Plateau, Tab.10b,11b,14b. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Procellariidae. 1172 records from Fungi collection of the Botanical Museum of the University of Oulu. 33 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Stylops (BNHS) â 1930-1971. 324 records from Alterra (NL) - Microarthropods inventory in Heathland. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 17 records from (Table 4) Total phytoplankton biomass, biomass of certain algal groups in the upper mixed layer and the water column, and contribution of the algal groups to total biomass of phytoplankton in the southwest Kara Sea on August 9-12, 2007. 659 records from EcoRecord - Caddisfly (Trichoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1 records from Orthoptera - SMF. 40725 records from Mycol
Keywords: GBIF; biodiversity; species occurrences